Flexographic printing plate and method for producing the same
The flexographic printing original plate with a specific intermediate layer design addresses pinholes and tackiness issues, ensuring stable relief image size and quick removal, enhancing the reliability and reproducibility of flexographic printing.
Patent Information
- Application Number
- JP2023511287
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-30
- Filing Date
- 2022-03-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-03-28
AI Technical Summary
Existing flexographic printing technologies face issues with pinholes in the infrared ablation layer, leading to unintended image formation and size inconsistencies due to defects, increased tackiness, and development residue re-adhesion, which are exacerbated by storage conditions and lamination processes.
A flexographic printing original plate design featuring a photosensitive resin composition layer, an intermediate layer with specific tensile properties, and an infrared ablation layer, where the intermediate layer has a water contact angle of 60° to 90° and includes emulsion compounds with a glass transition temperature of 30°C or higher, along with optional emulsion compounds below 10°C, inorganic layered compounds, and crosslinking agents, to enhance adhesion, prevent pinholes, and facilitate quick removal during development.
The solution ensures stable relief image size and prevents development residue re-adhesion, maintaining image quality regardless of storage conditions by quickly removing the infrared ablation layer and intermediate layer during development, thus improving the reliability and reproducibility of flexographic printing.
Smart Images

Figure 0007618781000004 
Figure 0007618781000005 
Figure 0007618781000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a flexographic printing plate precursor and a method for producing a flexographic printing plate. [Background technology]
[0002] In recent years, in the field of flexographic printing, CTP (Computer to Plate) technology has been developed and has become common. In the CTP technology, a master plate for manufacturing a flexographic printing plate is generally formed by laminating a photosensitive resin composition layer, an intermediate layer, an infrared ablation layer, and a cover film in this order on a substrate such as a PET resin.
[0003] The manufacture of a flexographic printing plate using the CTP technique is carried out, for example, as follows. First, a uniform cured layer is provided by performing back exposure in which ultraviolet light is irradiated onto the entire surface of the photosensitive resin composition layer through a substrate made of a film such as PET resin. Next, the cover film on the infrared ablation layer is peeled off to expose the infrared ablation layer, and a part of the infrared ablation layer is removed by irradiating it with a laser to draw, thereby preparing an image mask. Furthermore, relief exposure is performed in which ultraviolet light is irradiated onto the photosensitive resin composition layer through the image mask, thereby photocuring the part from which the infrared ablation layer has been removed. Thereafter, the unexposed parts (i.e., the parts not photocured) of the infrared ablation layer, intermediate layer, and photosensitive resin composition layer that are no longer necessary are dissolved or swelled in a developer and removed by applying an external force such as a brush, forming a relief image that is a desired image, thereby obtaining a flexographic printing plate.
[0004] In the manufacture of the above-mentioned flexographic printing plate, it is important that the infrared ablation layer is free of defects (hereinafter, also referred to as pinholes or PH). If there are pinholes in the infrared ablation layer, the photosensitive resin composition layer in contact with the pinholes will be exposed during relief exposure, resulting in the formation of an unintended image and the formation of a large relief image against the intention.
[0005] Methods for providing the infrared ablation layer on the photosensitive resin composition layer include a method in which the infrared ablation layer is directly applied to the photosensitive resin composition layer, as well as a method in which the infrared ablation layer is applied to a cover sheet, the infrared ablation layer side is attached to the photosensitive resin composition layer, and the layers are laminated by transfer.
[0006] However, there is a problem in that pinholes may occur due to impacts during storage and transportation of the cover sheet coated with the infrared ablation layer, and also due to the lamination temperature and pressure when bonding with the photosensitive resin composition layer, or due to contact with the kneaded extrusion resin.
[0007] In view of such problems, Patent Document 1 proposes a flexographic printing original plate in which an intermediate layer made of water-dispersible latex is provided between the above-mentioned photosensitive resin composition layer and the infrared ablation layer. By providing an intermediate layer of flexible and heat-resistant water-dispersible latex on the infrared ablation layer, it is possible to protect the cover sheet from impacts during storage and transportation, and from the lamination temperature and pressure when bonding it to the photosensitive resin composition layer, and to prevent the occurrence of pinholes.
[0008] It is also important that the infrared ablation layer has low adhesion. However, during storage of the flexographic printing original plate, low molecular weight components in the photosensitive resin composition may unintentionally migrate to the infrared ablation layer, which may increase the adhesion of the infrared ablation layer.
[0009] If the adhesiveness of the infrared ablation layer increases, when the cover film is peeled off to expose the infrared ablation layer during the production of a flexographic printing plate, the adhesion between the cover film and the infrared ablation layer will be strong, and the cover film may not be peeled off normally, which may result in pinholes.
[0010] Furthermore, when the unexposed portions of the photosensitive resin composition layer are removed during the production of a flexographic printing plate, there is a risk of defects in which residue from the infrared ablation layer re-adheres onto the relief image.
[0011] To address such problems, it is effective to provide an intermediate layer between the infrared ablation layer and the photosensitive resin composition layer using a material with high crystallinity in order to prevent mass transfer between the photosensitive resin composition layer and the infrared ablation layer. For example, Patent Document 2 proposes an intermediate layer made of a polyvinyl alcohol resin. Patent Document 3 proposes an intermediate layer made of a polyvinyl alcohol resin and a polyamide resin. These intermediate layers also prevent oxygen in the air from being supplied to the photosensitive resin composition layer, and can stably form a relief image. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2020-140182 A [Patent Document 2] JP 2013-156495 A [Patent Document 3] JP 2020-46568 A Summary of the Invention [Problem to be solved by the invention]
[0013] However, although the water-dispersible latex resin proposed in Patent Document 1 is flexible, highly scratch-resistant, and can prevent the occurrence of pinholes, the intermediate layer is hydrophobic and therefore difficult to dissolve or swell in an aqueous developer, making it difficult to remove during development.
[0014] In addition, the polyvinyl alcohol resin proposed in Patent Document 2 and the polyamide resin proposed in Patent Document 3 have good heat resistance and are hydrophilic, and therefore have good solubility in aqueous developers and can be developed quickly. However, since their crystal structures are derived from hydrogen bonds, they are inherently prone to absorbing water, and there was an issue that the plasticity of the intermediate layer increases when stored under high humidity conditions.
[0015] If the plasticity of the intermediate layer increases, the function of preventing mass transfer decreases, the adhesion of the infrared ablation layer increases, and there is a risk of defects in that the development residue of the infrared ablation layer reattaches onto the relief image. Furthermore, there is a problem that the blocking ability of oxygen in the atmosphere decreases, and the relief image formed becomes smaller than the desired size.
[0016] In view of the problems with the conventional technology, the present invention aims to provide a flexographic printing original plate in which the infrared ablation layer and intermediate layer can be quickly removed during development, the size of the relief image is stable regardless of the storage environment, and development residue from the infrared ablation layer does not re-adhere, and a method for producing a flexographic printing plate using the flexographic printing original plate. [Means for solving the problem]
[0017] As a result of intensive research into solving the above-mentioned problems, the inventors discovered that the above-mentioned problems can be solved by a flexographic printing plate precursor in which an intermediate layer has tensile properties within a specified numerical range, and thus completed the present invention.
[0018] That is, the present invention is as follows. [1] A support; A photosensitive resin composition layer on the support; The middle class, an infrared ablation layer, in that order; The intermediate layer was molded into a No. 8 dumbbell shape having a thickness of 100 μm in accordance with JIS K 6251 (2017) and measured, and the tensile stress-strain curve was The elongation to the breaking point is 5% or more and 200% or less, The elongation at the point where the stress is maximum is 3% or more and 200% or less, The maximum stress is 1.0 MPa or more and 15 MPa or less. Flexographic printing plate. [2] The intermediate layer has a water contact angle of 60° or more and 90° or less at the interface with the infrared ablation layer 3 minutes after droplet landing. The flexographic printing plate precursor according to [1]. [3] The intermediate layer has a water contact angle of 70° or more at the interface with the infrared ablation layer 3 minutes after droplet landing. The flexographic printing plate precursor according to [1] or [2]. [4] A support; A photosensitive resin composition layer on the support; The middle class, an infrared ablation layer, in that order; The intermediate layer has a water contact angle of 70° or more and 90° or less at the interface with the infrared ablation layer 3 minutes after droplet landing. Flexographic printing plate. [5] the intermediate layer contains an emulsion compound (A) having a glass transition temperature (Tg) of 30° C. or higher in an amount of 10% by mass or more and 95% by mass or less based on the total amount of the intermediate layer; The flexographic printing plate precursor according to any one of [1] to [4]. [6] The acid value of the emulsion compound (A) is 20 mgKOH / g or more and 100 mgKOH / g or less. The flexographic printing plate precursor according to [5]. [7] The number average molecular weight of the emulsion compound (A) is 2,000 or more and 50,000 or less. The flexographic printing plate precursor according to [5] or [6]. [8] The emulsion compound (A) contains a polyester emulsion. The flexographic printing plate precursor according to any one of [1] to [7]. [9] The emulsion compound (A) is a copolymer polyester emulsion containing an aromatic polycarboxylic acid component as a copolymer component and having a carboxyl group and / or a sulfonate group. The flexographic printing plate precursor according to [8].
[10] the intermediate layer further contains an emulsion compound (B) having a glass transition temperature (Tg) of 10° C. or lower in an amount of 10% by mass or more and 70% by mass or less, based on the total amount of the intermediate layer; The flexographic printing plate precursor according to any one of [1] to [9].
[11] The emulsion compound (B) is at least one emulsion compound selected from the group consisting of a polyurethane emulsion, a polybutadiene latex, a styrene-butadiene copolymer latex, and an acrylonitrile-butadiene copolymer latex. The flexographic printing plate precursor according to
[10] .
[12] The ratio of the emulsion compound (A) to the emulsion compound (B) is 1.0 or more and 2.3 or less. The flexographic printing plate precursor according to
[10] or
[11] .
[13] The intermediate layer further contains an inorganic layered compound (C). The flexographic printing plate precursor according to any one of [1] to
[12] .
[14] The intermediate layer further comprises a crosslinking agent (D). The flexographic printing plate precursor according to any one of [1] to
[13] .
[15] The thickness of the intermediate layer is greater than 2 μm and less than 30 μm. The flexographic printing plate precursor according to any one of [1] to
[14] .
[16] An infrared irradiation step of laser ablating the infrared ablation layer of the flexographic printing original plate according to any one of [1] to
[15] to produce a negative pattern; an exposure step of selectively exposing the photosensitive resin composition layer through the negative pattern; A development step of removing unexposed portions of the photosensitive resin composition layer. A method for manufacturing a flexographic printing plate.
[17]
[16] A method for producing a flexographic printing plate by the method for producing a flexographic printing plate according to
[16] , comprising: a printing plate production step; and a printing step using the flexographic printing plate produced by the printing plate production step. Flexographic printing method. Effect of the Invention
[0019] According to the present invention, it is possible to provide a flexographic printing original plate which can be quickly removed during development of the infrared ablation layer and intermediate layer, in which the size of the relief image is stable regardless of the storage environment, and in which development residue of the infrared ablation layer does not re-adhere, and a method for producing a flexographic printing plate using the flexographic printing original plate. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a schematic cross-sectional view of a flexographic printing original plate according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a method for producing a flexographic printing plate using the flexographic printing original plate of the present embodiment. [Diagram 3] FIG. 2 is a schematic diagram showing another embodiment of a method for producing a flexographic printing plate using the flexographic printing plate precursor of the present embodiment. [Figure 4] FIG. 2 is a tensile stress-strain curve diagram of Examples 2 and 6 and Comparative Example 1. [Diagram 5] FIG. 1 is a tensile stress-strain curve of Example 2. [Figure 6] FIG. 1 is a tensile stress-strain curve of Example 6. [Figure 7] FIG. 2 is a tensile stress-strain curve of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, the embodiments for carrying out the present invention will be described in detail, but the present invention is not limited thereto, and various modifications are possible without departing from the scope of the present invention. Hereinafter, the flexographic printing plate precursors of the first and second embodiments will be described, but when there is no particular distinction between them, they will be referred to as "the present embodiment".
[0022] 1. First embodiment: Flexographic printing plate The flexographic printing plate of the first embodiment comprises a support, and on the support, a photosensitive resin composition layer, an intermediate layer, and an infrared ablation layer, in that order. In a tensile stress-strain curve diagram of the intermediate layer measured after being molded into a No. 8 dumbbell shape with a thickness of 100 μm in accordance with JIS K 6251 (2017), the intermediate layer has an elongation to the breaking point of 5% or more and 200% or less, an elongation at the point where the stress is maximum of 3% or more and 200% or less, and a maximum stress value of 1.0 MPa or more and 15 MPa or less.
[0023] FIG. 1 shows a schematic cross-sectional view of the flexographic printing plate of the first embodiment. The flexographic printing plate 10 of the first embodiment is formed by sequentially laminating a support 11, a photosensitive resin composition layer 12 on which the uneven pattern of the flexographic printing plate is formed, an intermediate layer 13 that suppresses pinholes from being generated in the infrared ablation layer, and an infrared ablation layer 14 that functions as a mask when the uneven pattern of the flexographic printing plate is formed. A functional layer such as an adhesive layer may be provided between these layers as necessary. The configuration of the flexographic printing plate of the first embodiment will be described in detail below.
[0024] 1.1.Support The support used in the flexographic printing plate precursor of the first embodiment is not particularly limited, but examples thereof include polypropylene film, polyethylene film, polyester films such as polyethylene terephthalate and polyethylene naphthalate, and polyamide films, etc. Among these, polyester films are preferred as the support.
[0025] The thickness of the support is preferably 50 μm to 300 μm.
[0026] Furthermore, for the purpose of increasing the adhesive strength between the support and the photosensitive resin composition layer, an adhesive layer may be provided between the support and the photosensitive resin composition layer.
[0027] The material for the adhesive layer is not particularly limited, but examples thereof include compositions having a binder polymer such as polyurethane, polyamide, or thermoplastic elastomer, and an active adhesive component such as an isocyanate compound or an ethylenically unsaturated compound.
[0028] Furthermore, various auxiliary additives such as plasticizers, thermal polymerization inhibitors, ultraviolet absorbers, antihalation agents, light stabilizers, photopolymerization initiators, photopolymerizable monomers, dyes, etc. may be added to the adhesive layer.
[0029] In order to further increase the adhesive strength between the adhesive layer and the support, at least one undercoat layer may be provided between the adhesive layer and the support.
[0030] 1.2. Photosensitive resin composition layer The photosensitive resin composition layer constituting the flexographic printing original plate of the first embodiment is useful for any of solvent development, water development, and heat development.
[0031] The material of the photosensitive resin composition layer is not particularly limited, but a photosensitive resin composition containing, for example, a thermoplastic elastomer (a-1), a photopolymerizable monomer (a-3), and a photopolymerization initiator (a-4) can be preferably used. In addition to the upper components, the photosensitive resin composition layer may contain, as necessary, a liquid diene (a-5), a silicone compound (a-6), etc.
[0032] When the development step is carried out in an aqueous developer, the photosensitive resin composition layer preferably further contains polymer particles (a-2).
[0033] These (a-1) to (a-6) will be described in detail below, but as these components, for example, those described in JP 2018-120131 A may be used.
[0034] 1.2.1. Thermoplastic elastomer (a-1) The thermoplastic elastomer (a-1) is not particularly limited, but may be, for example, a thermoplastic elastomer having a structural unit derived from a conjugated diene and / or a vinyl aromatic hydrocarbon. The thermoplastic elastomer may be a homopolymer or a copolymer. In the case of a copolymer, the thermoplastic elastomer may be a random polymer or a block polymer.
[0035] Among these, thermoplastic elastomers containing at least one polymer block mainly composed of a conjugated diene and at least one polymer block mainly composed of a vinyl aromatic hydrocarbon are preferred.
[0036] The term "mainly composed of" as used throughout this specification means that 60% by weight or more of a polymer block is composed of a given monomer.
[0037] In the polymer block mainly composed of a conjugated diene, the content of the conjugated diene unit in the polymer block is preferably 80% by mass or more, and more preferably 90% by mass or more.
[0038] The conjugated diene is not particularly limited, but examples thereof include monomers such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 4,5-diethyl-1,3-octadiene, 3-butyl-1,3-octadiene, and chloroprene. Among these, 1,3-butadiene is particularly preferred from the viewpoint of wear resistance. These monomers may be used alone or in combination of two or more.
[0039] In the polymer block mainly composed of a conjugated diene, the vinyl content is preferably 5 to 50 mol%, more preferably 8 to 50 mol%, and even more preferably 10 to 40 mol%, based on the total amount of conjugated diene units from the viewpoint of printing plate formability. Here, the "vinyl content" refers to, for example, the content of 1,2-butadiene or 3,4-isoprene.
[0040] The number average molecular weight of the polymer block mainly composed of a conjugated diene is preferably from 20,000 to 250,000, more preferably from 30,000 to 200,000, and even more preferably from 40,000 to 150,000, from the viewpoint of printing durability.
[0041] The polymer block mainly made of conjugated diene may contain an alkylene unit. The method of introducing the alkylene unit is not particularly limited, but examples thereof include a method of polymerizing a monoolefin such as ethylene or butylene as a raw material monomer of the polymer block mainly made of conjugated diene, and a method of hydrogenating the conjugated diene polymer block. In particular, from the viewpoint of availability, the method of hydrogenating the polymer block mainly made of conjugated diene is preferred.
[0042] In the polymer block mainly composed of a conjugated diene, the content of the alkylene unit is preferably 5 to 50 mol%, more preferably 10 to 35 mol%, and even more preferably 10 to 25 mol%, based on the total amount of the monomer units constituting the polymer block. When the content of the alkylene unit is 5 mol% or more, the solvent resistance tends to be further improved. Also, when the content of the alkylene unit is 50 mol% or less, the transparency of the photosensitive resin composition layer tends to be further improved.
[0043] The polymer block mainly composed of conjugated diene preferably contains an alkylene unit, more preferably contains all of a 1,4-butadiene unit, a 1,2-butadiene (vinyl) unit and a butylene (alkylene) unit. In this case, the polymer block mainly composed of conjugated diene more preferably contains 25 to 70 mol% of a 1,4-butadiene unit, 0 to 50 mol% of a 1,2-butadiene (vinyl) unit and 10 to 50 mol% of a butylene unit. Such a polymer block can be obtained by hydrogenating a polymer block mainly composed of butadiene.
[0044] The conjugated diene, the vinyl content of the conjugated diene, and the content and ratio of vinyl aromatic hydrocarbons were measured using a nuclear magnetic resonance spectrometer ( 1 H-NMR can be used to measure the
[0045] The vinyl aromatic hydrocarbon is not particularly limited, but examples thereof include monomers such as styrene, t-butylstyrene, divinylbenzene, 1,1-diphenylstyrene, N,N-dimethyl-p-aminoethylstyrene, N,N-diethyl-p-aminoethylstyrene, vinylpyridine, p-methylstyrene, tertiary butylstyrene, α-methylstyrene, and 1,1-diphenylethylene. Styrene is particularly preferred because it allows the flexographic printing plate precursor to be smoothly molded at a relatively low temperature (hereinafter, also referred to as "high moldability"). These monomers may be used alone or in combination of two or more.
[0046] The number average molecular weight of the polymer block mainly composed of vinyl aromatic hydrocarbon is preferably 100,000 or less from the viewpoint of preventing orientation from appearing on the printing plate, and is preferably 3,000 or more from the viewpoint of chipping resistance during plate making and printing. The number average molecular weight of the polymer block mainly composed of vinyl aromatic hydrocarbon is more preferably 5,000 to 80,000, and further preferably 5,000 to 60,000.
[0047] The content of vinyl aromatic hydrocarbon in the block copolymer is preferably 13 to 25 mass%, more preferably 15 to 24 mass%, and even more preferably 16 to 23 mass%, based on the total amount of the block copolymer. By making the content of vinyl aromatic hydrocarbon 25 mass% or less, the photosensitive resin composition tends to have high moldability, the convex portion of the printing plate tends to have high chipping resistance, and the printing plate hardness tends to be high when ink components are attached. On the other hand, by making the content of vinyl aromatic hydrocarbon 13 mass% or more, the cold flow resistance of the flexographic printing plate precursor tends to be further improved.
[0048] From the viewpoint of printing durability during printing, the content of the thermoplastic elastomer (a-1) in the photosensitive resin composition layer is preferably 15 to 90 mass%, more preferably 15 to 80 mass%, and even more preferably 20 to 75 mass%, when the total amount of the photosensitive resin composition is 100 mass%.
[0049] 1.2.2. Polymer particles (a-2) Polymer particles (a-2) are polymer particles in which monomer is internally crosslinked. Such polymer particles are not particularly limited, but can be, for example, obtained by dispersing polymer particles as dispersoid in water to prepare water-dispersible latex by emulsion polymerization, and removing water from the obtained water-dispersible latex.
[0050] The monomer constituting the polymer particle (a-2) is not particularly limited as long as it has a polymerizable double bond, and examples thereof include monobasic acid monomers, polybasic acid monomers, conjugated dienes, aromatic vinyl compounds, (meth)acrylic acid esters, monomers having a hydroxyl group, unsaturated dibasic acid alkyl esters, maleic anhydride, vinyl cyanide compounds, (meth)acrylamide and its derivatives, vinyl esters, vinyl ethers, vinyl halides, basic monomers having an amino group, vinylpyridine, olefins, silicon-containing α,β-ethylenically unsaturated monomers, allyl compounds, etc. In addition, the monomer constituting the polymer particle (a-2) may contain a reactive emulsifier used in emulsion polymerization described later.
[0051] The monobasic acid monomer is not particularly limited, but examples thereof include monomers having a carboxyl group, such as acrylic acid, methacrylic acid, crotonic acid, vinylbenzoic acid, and cinnamic acid; and monomers having a sulfonic acid group, such as styrenesulfonic acid.
[0052] The content of the monobasic acid monomer is preferably 1 to 30 mass %, more preferably 2 to 20 mass %, even more preferably 3 to 15 mass %, and still more preferably 5 to 10 mass %, based on the total amount of the polymer particles (a-2).
[0053] The polybasic acid monomer is not particularly limited, but examples thereof include monomers having two or more carboxyl groups, such as itaconic acid, fumaric acid, maleic acid, citraconic acid, and muconic acid; monomers having an acid anhydride group; and monomers having a polybasic acid group such as a phosphate group.
[0054] The conjugated diene is not particularly limited, but examples thereof include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 2-methyl-1,3-butadiene, 1,3-pentadiene, chloroprene, 2-chloro-1,3-butadiene, and cyclopentadiene.
[0055] The content of the conjugated diene is preferably from 45 to 75% by mass, more preferably from 50 to 70% by mass, and further preferably from 55 to 65% by mass, based on the total amount of the polymer particles (a-2).
[0056] The aromatic vinyl compound is not particularly limited, but examples thereof include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, vinyltoluene, vinylxylene, bromostyrene, vinylbenzyl chloride, pt-butylstyrene, chlorostyrene, alkylstyrene, divinylbenzene, and trivinylbenzene.
[0057] The content of the aromatic vinyl compound is preferably from 3 to 25% by mass, more preferably from 5 to 20% by mass, and further preferably from 7.5 to 15% by mass, based on the total amount of the polymer particles (a-2).
[0058] The (meth)acrylic acid ester is not particularly limited, and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, n-amyl (meth)acrylate, isoamylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate, cyclohexyl (meth)acrylate, and the like. ) acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, 2-ethyl-hexyl (meth)acrylate, glycidyl (meth)acrylate, ethylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexane Diol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, allyl (meth)acrylate, bis(4-acryloxypolyethoxyphenyl)propane , methoxypolyethylenglycol (meth)acrylate, β-(meth)acryloyloxyethyl hydrogen phthalate, β-(meth)acryloyloxyethyl hydrogen succinate, 3-chloro-2-hydroxypropyl (meth)acrylate, stearyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, 2-hydroxy-1,3-di(meth)acryloxypropane, 2,2-bis[4-((meth)acryloxyethoxy)phenyl]propane, 2,Examples of the acrylate copolymer include 2-bis[4-((meth)acryloxy-diethoxy)phenyl]propane, 2,2-bis[4-((meth)acryloxy-polyethoxy)phenyl]propane, and isobornyl(meth)acrylate.
[0059] The content of the (meth)acrylic acid ester is preferably from 10 to 35% by mass, more preferably from 15 to 30% by mass, and further preferably from 20 to 25% by mass, based on the total amount of the polymer particles (a-2).
[0060] The monomer having a hydroxyl group is not particularly limited, and examples thereof include ethylenic monocarboxylic acid alkyl ester monomers such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 1-hydroxypropyl acrylate, 1-hydroxypropyl methacrylate, and hydroxycyclohexyl (meth)acrylate.
[0061] The unsaturated dibasic acid alkyl ester is not particularly limited, but examples thereof include crotonic acid alkyl ester, itaconic acid alkyl ester, fumaric acid alkyl ester, and maleic acid alkyl ester.
[0062] The vinyl cyanide compound is not particularly limited, but examples thereof include acrylonitrile and methacrylonitrile.
[0063] The (meth)acrylamide and its derivatives are not particularly limited, but examples thereof include (meth)acrylamide, N-methylol(meth)acrylamide, and N-alkoxy(meth)acrylamide.
[0064] The vinyl esters are not particularly limited, but examples thereof include vinyl acetate, vinyl butyrate, vinyl stearate, vinyl laurate, vinyl myristate, vinyl propionate, vinyl versatate, and the like.
[0065] The vinyl ethers are not particularly limited, but examples thereof include methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, amyl vinyl ether, and hexyl vinyl ether.
[0066] The vinyl halides are not particularly limited, but examples thereof include vinyl chloride, vinyl bromide, vinyl fluoride, vinylidene chloride, and vinylidene fluoride.
[0067] The basic monomer having an amino group is not particularly limited, but examples thereof include aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate.
[0068] The olefin is not particularly limited, but examples thereof include ethylene.
[0069] The silicon-containing α,β-ethylenically unsaturated monomer is not particularly limited, but examples thereof include vinyltrichlorosilane, vinyltriethoxysilane, and the like.
[0070] The allyl compound is not particularly limited, but examples thereof include allyl esters and diallyl phthalates.
[0071] In addition, a monomer having three or more double bonds, such as triallyl isocyanurate, can also be used.
[0072] These monomers may be used alone or in combination of two or more. Among them, it is preferable to use a monomer having an acidic group such as a monobasic acid monomer or a polybasic acid monomer (hereinafter simply referred to as an "acidic monomer") and a monomer having a hydrophobic group such as a conjugated diene, an aromatic vinyl compound, or a (meth)acrylic acid ester (hereinafter simply referred to as a "hydrophobic monomer"). The conjugated diene, aromatic vinyl compound, and (meth)acrylic acid ester corresponding to the above hydrophobic monomers have a hydrocarbon group, and those having a hydrophilic group such as a hydroxyl group are excluded from the hydrophobic monomer even if they are (meth)acrylic acid esters or the like.
[0073] The content of the acidic monomer is preferably 1 to 30% by mass, more preferably 2 to 20% by mass, even more preferably 3 to 15% by mass, and even more preferably 5 to 10% by mass, based on the total amount of the polymer particles (a-2). By making the content of the acidic monomer 1% by mass or more, the aqueous development performance tends to be further improved. In addition, by making the content 30% by mass or less, an increase in the moisture absorption amount of the photosensitive resin composition and an increase in the swelling amount of the ink can be prevented, and deterioration of the processability during mixing of the photosensitive resin composition can be prevented.
[0074] The content of the monomer having a hydrophobic group is preferably 70 to 99 mass%, more preferably 80 to 98 mass%, further preferably 85 to 97 mass%, and further preferably 90 to 95 mass%. When the polymer particles (a-2) have such a composition, the rubber elasticity of the photosensitive resin composition tends to be further improved.
[0075] The polymer constituting the polymer particles (a-2) is not particularly limited, and examples thereof include polymers having a butadiene skeleton, such as polybutadiene, acrylonitrile-butadiene copolymer, styrene-butadiene copolymer, and (meth)acrylate-butadiene copolymer; polymers having an isoprene skeleton, such as polyisoprene and polychloroprene; polymers obtained by further polymerizing a monomer having a carboxyl group and / or a hydroxyl group on the polymer having the butadiene skeleton or isoprene skeleton; polymers obtained by further polymerizing a (meth)acrylic acid ester on the polymer having the butadiene skeleton or isoprene skeleton; polymers obtained by further polymerizing a (meth)acrylic acid ester and a monomer having a carboxyl group and / or a hydroxyl group on the polymer having the butadiene skeleton or isoprene skeleton; polyurethane, vinylpyridine polymer, butyl polymer, thiokol polymer, acrylate polymer, and natural rubber.
[0076] The monomer having a carboxyl group herein means the above-mentioned monobasic acid monomer and / or polybasic acid monomer.
[0077] Among these, preferred are polymers having a butadiene skeleton, polymers having an isoprene skeleton, and polymers obtained by further polymerizing the above-mentioned polymers having a butadiene skeleton or an isoprene skeleton with a (meth)acrylic acid ester and / or a monomer having a carboxyl group and / or a hydroxyl group, and more preferred are polymers obtained by further polymerizing the above-mentioned polymers having a butadiene skeleton with a (meth)acrylic acid ester and / or a monomer having a carboxyl group and / or a hydroxyl group. The polymer particles (a-2) may be used alone or in combination of two or more kinds.
[0078] The average particle size of the polymer particles (a-2) is preferably 500 nm or less, more preferably 100 nm or less. When the average particle size is 500 nm or less, the aqueous developability of the flexographic printing plate precursor tends to be improved.
[0079] The toluene gel fraction of the polymer particles (a-2) is preferably 60% to 99%. If the toluene gel fraction is 60% or more, the resulting printing plate tends to have sufficient strength for practical use. If the toluene gel fraction is 99% or less, the mixability of the polymer particles (a-2) and the thermoplastic elastomer (a-1) tends to be good.
[0080] Here, the toluene gel fraction refers to a mass fraction (%) obtained by dropping an appropriate amount of a dispersion of about 30% by mass of polymer particles (a-2) onto a Teflon (registered trademark) sheet and drying at 130°C for 30 minutes to obtain 0.5 g of polymer particles (a-2), immersing this in 30 mL of toluene at 25°C, shaking for 3 hours using a shaker, filtering through a 320 SUS mesh, and drying the non-passing portion at 130°C for 1 hour, and dividing the mass by 0.5 (g).
[0081] From the viewpoint of developability during production of a printing plate, the content of the polymer particles (a-2) is preferably 10 to 70 mass%, more preferably 15 to 60 mass%, and even more preferably 20 to 50 mass%, when the total amount of the photosensitive resin composition is taken as 100 mass%.
[0082] (Production method of polymer particles (a-2)) The synthesis method of polymer particles (a-2) is not particularly limited, but for example, it is preferable that the polymer is synthesized by emulsion polymerization.As the emulsion polymerization method of polymer particles (a-2), a method can be mentioned in which a predetermined amount of water, emulsifier, and other additives are charged in advance into a reaction system adjusted to a polymerization temperature, and a polymerization initiator, a monomer, an emulsifier, a regulator, etc. are added to this system by batch operation or continuous operation into the reaction system.In addition, a predetermined amount of seed latex, polymerization initiator, monomer, and other regulators may be charged in advance into the reaction system of emulsion polymerization.
[0083] In addition, by devising a method for adding a monomer, an emulsifier, other additives, and a regulator to the reaction system, it is possible to change the layer structure of the synthesized polymer particles stepwise. In this case, representative physical properties of the structure of each layer include hydrophilicity, glass transition point, molecular weight, crosslink density, etc. In addition, the number of steps of this layer structure is not particularly limited.
[0084] Hereinafter, each component other than the monomers already mentioned will be described.
[0085] The emulsifier (surfactant) used during emulsion polymerization is not particularly limited, and examples thereof include reactive emulsifiers and / or non-reactive emulsifiers. Among these, it is preferable to use a reactive emulsifier.
[0086] The reactive emulsifier is preferably a reactive emulsifier that contains a radically polymerizable double bond, a hydrophilic functional group, and a hydrophobic group in its molecular structure and has emulsifying, dispersing, and wetting functions similar to those of general emulsifiers. Among these, an emulsifier (surfactant) that gives an average particle size of 5 to 500 nm of the resulting polymer particles when 0.1 parts by mass or more of the reactive emulsifier is used per 100 parts by mass of all monomers other than the reactive emulsifier is preferred.
[0087] The hydrophilic functional group possessed by the reactive emulsifier is not particularly limited, and examples thereof include anionic groups such as sulfate group, nitrate group, phosphate group, borate group, and carboxyl group, cationic groups such as amino group, polyoxyalkylene chain structures such as polyoxyethylene, polyoxymethylene, and polyoxypropylene, and hydroxyl group, etc. Depending on the type of the hydrophilic functional group, the reactive emulsifier can be classified into anionic emulsifiers, nonionic emulsifiers, cationic emulsifiers, amphoteric emulsifiers, etc.
[0088] The hydrophobic group of the reactive emulsifier is not particularly limited, and examples thereof include an alkyl group, a phenyl group, etc. The radically polymerizable double bond of the reactive emulsifier is not particularly limited, and examples thereof include a vinyl group, an acryloyl group, a methacryloyl group, etc. The molecular structure may contain multiple types of radically polymerizable double bonds, hydrophilic functional groups, and hydrophobic groups.
[0089] The reactive emulsifier may be a commercially available surfactant. Examples of commercially available anionic surfactants include, but are not limited to, Adeka Reasoap SE (manufactured by ADEKA), Aqualon HS, BC, and KH (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), Latemul S (manufactured by Kao Corporation), Antox MS (manufactured by Nippon Nyukazai Co., Ltd.), Adeka Reasoap SDX and PP (manufactured by ADEKA), Hitenol A (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), Eleminol RS (manufactured by Sanyo Chemical Industries Co., Ltd.), and Spinomer (manufactured by Toyo Soda Kogyo Co., Ltd.). Examples of commercially available nonionic surfactants include, but are not limited to, Aqualon RN and Noigen N (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), Adeka Reasoap NE (manufactured by ADEKA), and the like. These may be used alone or in combination of two or more types.
[0090] The amount of reactive emulsifier used is preferably 1 to 20 parts by mass per 100 parts by mass of polymer particles (a-2) calculated from the amount of raw materials charged. When the amount of reactive emulsifier used is 1 part by mass or more, the image reproducibility of the obtained printing plate tends to improve. Also, when the amount of reactive emulsifier used is 20 parts by mass or less, the printing resistance of the obtained printing plate tends to improve.
[0091] The non-reactive emulsifier is not particularly limited, but examples thereof include anionic surfactants such as fatty acid soap, rosin acid soap, sulfonate, sulfate, phosphate ester, polyphosphate ester, and salicosinic acid acyl; cationic surfactants such as nitrile oil derivatives, oil derivatives, fatty acid derivatives, and α-olefin derivatives; and nonionic surfactants such as alcohol ethoxylates, alkylphenol ethoxylates, propoxylates, aliphatic alkanolamides, alkyl polyglycosides, polyoxyethylene sorbitan fatty acid esters, and oxyethylene oxypropylene block copolymers. These may be used alone or in combination of two or more.
[0092] The sulfonate is not particularly limited, but may be, for example, alkyl sulfonate, alkyl sulfate, alkyl sulfosuccinate, polyoxyethylene alkyl sulfate, sulfonated fats and oils, alkyl diphenyl ether disulfonate, α-olefin sulfonate, alkyl glyceryl ether sulfonate, N-acyl methyl taurate, etc. Examples of non-reactive emulsifiers other than those described above are not particularly limited, but may be, for example, those described in "Surfactant Handbook (Takahashi, Namba, Koike, Kobayashi: Kogyo Tosho, 1972)".
[0093] The amount of the non-reactive emulsifier used is preferably less than 1 part by mass per 100 parts by mass of the polymer particles (a-2) calculated from the amount of the raw materials charged. By using an amount of the non-reactive emulsifier of less than 1 part by mass, the resulting printing plate has an appropriate water swelling ratio, and it is possible to prevent a decrease in abrasion resistance when ink is attached and a decrease in image reproducibility after moisture absorption.
[0094] The polymerization initiator is not particularly limited, but may be, for example, a radical polymerization initiator. The radical polymerization initiator is not particularly limited, but may be, for example, a radical decomposition initiator in the presence of heat or a reducing substance to initiate addition polymerization of a monomer, and may be either an inorganic initiator or an organic initiator.
[0095] The radical polymerization initiator is not particularly limited, and examples thereof include water-soluble or oil-soluble peroxodisulfates, peroxides, azobis compounds, etc., and specifically include potassium peroxodisulfate, sodium peroxodisulfate, ammonium peroxodisulfate, hydrogen peroxide, t-butyl hydroperoxide, benzoyl peroxide, 2,2-azobisbutyronitrile, cumene hydroperoxide, etc. In addition, as the radical polymerization initiator, compounds described in POLYMER HANDBOOK (3rd edition), written by J. Brandrup and EH Immergut, published by John Willy & Sons (1989) can also be used. In addition, a so-called redox polymerization method can be adopted in which a reducing agent such as acidic sodium sulfite, ascorbic acid or its salt, erythorbic acid or its salt, or Rongalit is used in combination with the polymerization initiator. Among these, peroxodisulfates are suitable as the polymerization initiator.
[0096] The amount of the polymerization initiator used is usually 0.1 to 5.0% by mass, preferably 0.2 to 3.0% by mass, based on the total amount of monomers used in the polymerization of the polymer particles (a-2). When the amount of the polymerization initiator used is 0.1% by mass or more, high stability is obtained during the synthesis of the polymer particles (a-2). In addition, when the amount of the polymerization initiator used is 5.0% by mass or less, the moisture absorption amount of the photosensitive resin composition can be suppressed to a practically good range.
[0097] In the polymerization process of the polymer particles (a-2), a known chain transfer agent can be used. As the chain transfer agent, a chain transfer agent containing a sulfur element can be suitably used. As the chain transfer agent containing a sulfur element, there is no particular limitation, but for example, alkanethiols such as t-dodecyl mercaptan and n-dodecyl mercaptan; thioalkyl alcohols such as mercaptoethanol and mercaptopropanol; thioalkyl carboxylic acids such as thioglycolic acid and thiopropionic acid; thiocarboxylate alkyl esters such as thioglycolic acid octyl ester and thiopropionic acid octyl ester; and sulfides such as dimethyl sulfide and diethyl sulfide.
[0098] Other chain transfer agents are not particularly limited, but may include, for example, halogenated hydrocarbons such as terpinolene, dipentene, t-terpinene, and carbon tetrachloride. Among these chain transfer agents, alkanethiol is preferred because it has a high chain transfer rate and the physical properties of the resulting polymer are well balanced. These chain transfer agents may be used alone or in combination of two or more.
[0099] These chain transfer agents are mixed with the monomers and fed to the reaction system, or added alone at a predetermined time in a predetermined amount. The amount of these chain transfer agents used is preferably 0.1 to 10 mass% based on the total amount of monomers used in the polymerization of the polymer particles (a-2). By making the amount 0.1 mass% or more, the processability during mixing of the photosensitive resin composition is good, and by making the amount 10 mass% or less, the molecular weight of the polymer particles (a-2) can be made practically sufficient.
[0100] A polymerization inhibitor can be used for the polymerization of the polymer particles (a-2) as necessary. The polymerization inhibitor is a compound that reduces the radical polymerization rate by adding it to an emulsion polymerization system. More specifically, the polymerization inhibitor is a polymerization rate retarder, a polymerization inhibitor, a chain transfer agent with low radical reinitiation reactivity, and a monomer with low radical reinitiation reactivity. The polymerization inhibitor is generally used to adjust the polymerization rate and the physical properties of the latex. These polymerization inhibitors are added to the reaction system in a batch operation or a continuous operation. When the polymerization inhibitor is used, the strength of the latex coating is improved and the printing durability is improved. Although the details of the reaction mechanism are unknown, the polymerization inhibitor is considered to be closely related to the three-dimensional structure of the polymer, and it is presumed that this is effective in adjusting the physical properties of the latex coating.
[0101] The polymerization reaction inhibitor is not particularly limited, but examples thereof include quinones such as o-, m-, or p-benzoquinone; nitro compounds such as nitrobenzene, o-, m-, or p-dinitrobenzene; amines such as diphenylamine; catechol derivatives such as tertiary butylcatechol; 1,1-disubstituted vinyl compounds such as 1,1-diphenylethylene, α-methylstyrene, and 2,4-diphenyl-4-methyl-1-pentene; 1,2-disubstituted vinyl compounds such as 2,4-diphenyl-4-methyl-2-pentene and cyclohexene; etc. In addition, compounds described as polymerization inhibitors or polymerization inhibitors in "POLYMER HANDBOOK 3rd Ed. (J. Brandup, EH Immergut: John Wiley & Sons, 1989)" and "Revised Chemistry of Polymer Synthesis (Otsu: Kagaku Dojin, 1979.)" are also included.
[0102] Among these, 2,4-diphenyl-4-methyl-1-pentene (α-methylstyrene dimer) is particularly preferred from the viewpoint of reactivity. These polymerization reaction inhibitors may be used alone or in combination of two or more.
[0103] The amount of the polymerization reaction inhibitor used is preferably 10% by mass or less based on the total amount of monomers used in the polymerization of the polymer particles (a-2). By making the amount 10% by mass or less, a polymerization rate sufficient for practical use tends to be obtained.
[0104] During the synthesis of the polymer particles (a-2), various polymerization regulators such as a pH regulator and a chelating agent may be added, if necessary.
[0105] The pH adjuster is not particularly limited, but examples thereof include sodium hydroxide, potassium hydroxide, ammonium hydroxide, sodium hydrogen carbonate, sodium carbonate, and disodium hydrogen phosphate.
[0106] The chelating agent is not particularly limited, but examples thereof include sodium ethylenediaminetetraacetate.
[0107] Furthermore, other additives that may be added include various additives such as alkali-sensitive latex, viscosity reducers such as hexametaphosphoric acid, water-soluble polymers such as polyvinyl alcohol and carboxymethyl cellulose, thickeners, various anti-aging agents, ultraviolet absorbers, preservatives, bactericides, defoamers, dispersants such as sodium polyacrylate, water-resistant agents, metal oxides such as zinc oxide, crosslinking agents such as isocyanate compounds and epoxy compounds, lubricants, and water retention agents.
[0108] The method of adding these additives is not particularly limited, and they can be added either during or after the synthesis of the polymer particles (a-2).
[0109] The polymerization temperature in emulsion polymerization of the polymer particles (a-2) is usually 60 to 120° C. Polymerization may be performed at a lower temperature by redox polymerization, etc. Furthermore, a metal catalyst, such as divalent iron ions, trivalent iron ions, copper ions, etc., may be coexisted as an oxidation-reduction catalyst.
[0110] 1.2.3. Photopolymerizable monomer (a-3) The photopolymerizable monomer (a-3) is not particularly limited, but examples thereof include esters of acids such as acrylic acid, methacrylic acid, fumaric acid, and maleic acid; acrylamide and methacrylamide derivatives; allyl esters, styrene and its derivatives; and N-substituted maleimide compounds.
[0111] The photopolymerizable monomer (a-3) is not particularly limited, and examples thereof include diacrylates and dimethacrylates of alkanediols such as 1,6-hexanediol and 1,9-nonanediol; diacrylates and dimethacrylates of ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, polyethylene glycol, butylene glycol, and dicyclopentadienyl; trimethylolpropane tri(meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, isobornyl(meth)acrylate, phenoxypolyethylene glycol(meth)acrylate, pentaerythritol tetraacetate, and the like. Examples of the acrylate include methacrylate, N,N'-hexamethylenebisacrylamide and methacrylamide, styrene, vinyltoluene, divinylbenzene, diacrylphthalate, triallyl cyanurate, diethyl fumarate, dibutyl fumarate, dioctyl fumarate, distearyl fumarate, butyloctyl fumarate, diphenyl fumarate, dibenzyl fumarate, dibutyl maleate, dioctyl maleate, bis(3-phenylpropyl) fumarate, dilauryl fumarate, dibehenyl fumarate, and N-laurylmaleimide. These may be used alone or in combination of two or more.
[0112] From the viewpoint of even higher chipping resistance of the raised portions of the printing plate, the photopolymerizable monomer (a-3) is preferably a di(meth)acrylate monomer having two (meth)acrylate groups in one molecule. The content of such a di(meth)acrylate monomer is preferably 2.0 mass% or more, more preferably 2.0 to 20 mass%, and even more preferably 5.0 to 16 mass%, based on the total amount of the photosensitive resin composition.
[0113] From the viewpoint of obtaining bright prints, the content of the photopolymerizable monomer (a-3) is preferably 1 to 25 mass%, more preferably 5 to 20 mass%, and even more preferably 8 to 15 mass%, when the total amount of the photosensitive resin composition is taken as 100 mass%.
[0114] 1.2.4. Photopolymerization initiator (a-4) The photopolymerization initiator (a-4) is a compound that absorbs light energy and generates radicals. Various known photopolymerization initiators can be used, and various organic carbonyl compounds, and particularly aromatic carbonyl compounds, are preferred.
[0115] The photopolymerization initiator (a-4) is not particularly limited, and examples thereof include thioxanthones such as benzophenone, 4,4-bis(diethylamino)benzophenone, t-butylanthraquinone, 2-ethylanthraquinone, 2,4-diethylthioxanthone, isopropylthioxanthone, and 2,4-dichlorothioxanthone; diethoxyacetophenone, 2,2-dimethoxyphenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 1-hydroxycyclohexyl-phenyl ketone, 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one, and 2-benzyl-2-dimethylamino-1- Examples of the compounds include acetophenones such as (4-morpholinophenyl)-butanone, benzoin ethers such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether, acylphosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, methylbenzoyl formate, 1,7-bisacridinylheptane, 9-phenylacridine, and 2,6-di-t-butyl-p-cresol. These compounds may be used alone or in combination of two or more.
[0116] From the viewpoints of improving plate formability during plate making and obtaining bright prints, the content of the photopolymerization initiator (a-4) is preferably 0.1 to 10.0 mass%, more preferably 1.0 to 8.0 mass%, and even more preferably 1.5 to 5.0 mass%, when the total amount of the photosensitive resin composition is taken as 100 mass%.
[0117] As the photopolymerization initiator (a-4), a decomposition type photopolymerization initiator and a hydrogen abstraction type photopolymerization initiator may be used in combination. In order to improve the image reproducibility and abrasion resistance of the printing plate, the amount of the hydrogen abstraction type photopolymerization initiator in the photosensitive resin composition is preferably 1.0% by mass or less, and more preferably 0.5% by mass or less.
[0118] 1.2.5. Liquid diene (a-5) The photosensitive resin composition layer may contain a liquid diene (a-5). A liquid diene is a compound having a liquid carbon-carbon double bond. In this specification, the term "liquid" in "liquid diene" means a property of being easily fluid and deformed and being able to be solidified in the deformed shape by cooling, and is a term corresponding to an elastomer having a property of being instantly deformed in response to an external force when the external force is applied and recovering the original shape in a short time when the external force is removed.
[0119] The liquid diene (a-5) is not particularly limited, but examples thereof include liquid polybutadiene, liquid polyisoprene, modified liquid polybutadiene, modified liquid polyisoprene, liquid acrylonitrile-butadiene copolymer, and liquid styrene-butadiene copolymer. The liquid diene is a copolymer containing 50% by mass or more of a diene component.
[0120] Among these, from the viewpoint of the mechanical properties of the flexographic printing plate precursor of the first embodiment and the flexographic printing plate precursor using the same, liquid polybutadiene is preferred as the liquid diene (a-5).
[0121] The number average molecular weight of the liquid diene (a-5) is not particularly limited as long as it is liquid at 20°C. From the viewpoint of printing durability and handling of the flexographic printing plate obtained using the flexographic printing original plate of the first embodiment, the number average molecular weight is preferably 500 or more and 60,000 or less, more preferably 500 or more and 50,000 or less, and even more preferably 800 or more and 50,000 or less.
[0122] From the viewpoint of the printing durability of the flexographic printing plate precursor of the first embodiment and the flexographic printing plate using the same, the content of the liquid diene (a-5) in the photosensitive resin composition layer is preferably 10 to 40 mass%, more preferably 15 to 40 mass%, and even more preferably 20 to 40 mass%, when the total amount of the photosensitive resin composition layer (b) is taken as 100 mass%.
[0123] 1.2.6. Silicone compounds (a-6) Examples of the silicone compound (a-6) include silicone oil, a silane coupling agent, a silane compound, silicone rubber, silicone resin, etc. Among them, silicone oil is preferred because the components are easily transferred to the surface and it is highly effective in lowering the surface energy.
[0124] The silicone compound (a-6) is not particularly limited, and may be, for example, a compound having a polyalkylsiloxane such as polydimethylsiloxane or polydiethylsiloxane in the main chain. The silicone compound (a-6) may also be a compound having a polysiloxane structure in a part of the molecule. Furthermore, the silicone compound (a-6) may be a compound having a specific organic group introduced into the polysiloxane structure. Specifically, a compound having an organic group introduced into the side chain of the polysiloxane, a compound having an organic group introduced into both ends of the polysiloxane, a compound having an organic group introduced into one end of the polysiloxane, a compound having an organic group introduced into both the side chain and the end of the polysiloxane, etc. may be used.
[0125] The organic group to be introduced into the polysiloxane structure is not particularly limited, but examples thereof include an amino group, a carboxyl group, a carbinol group, an aryl group, an alkyl group, an alkoxycarbonyl group, an alkoxy group, a linear or branched alkyl group substituted with at least one aryl group, and a polyoxyalkylene group (hereinafter also referred to as a polyether group).
[0126] Among these, silicone compound (a-6) is more preferably a silicone oil having polysiloxane as a main skeleton and having at least one group selected from the group consisting of amino group, polyether group, and carbinol group at at least one end.By using such silicone compound (a-6), the transparency of the photosensitive resin composition layer tends to be improved.In addition, the commercially available product of such silicone compound is not particularly limited, but for example, KF-6000 manufactured by Shin-Etsu Chemical Co., Ltd. can be mentioned.
[0127] The content of the silicone compound (a-6) is preferably 0.1 to 5.0 mass %, more preferably 0.5 to 3.0 mass %, and further preferably 0.5 to 2.0 mass %, based on the total amount of the photosensitive resin composition layer.
[0128] 1.3. Middle Tier The flexographic printing original plate of the first embodiment has an intermediate layer between the photosensitive resin composition layer and the infrared ablation layer. When the unexposed parts of the photosensitive resin composition layer are washed out after the exposure, the intermediate layer is also removed at the same time.
[0129] The intermediate layer has a function of preventing diffusion of substances between the photosensitive resin composition layer and the infrared ablation layer (hereinafter, also referred to as "diffusion barrier property"). By blocking the diffusion of low molecular weight components from the photosensitive resin composition layer to the infrared ablation layer, an increase in the adhesiveness of the infrared ablation layer can be suppressed. By suppressing an increase in the adhesiveness of the infrared ablation layer, development residue from the infrared ablation layer is suppressed from re-adhering to the plate during development.
[0130] In addition, the intermediate layer preferably has a function of blocking oxygen in the air from diffusing into the photosensitive resin composition layer (hereinafter, also referred to as "oxygen blocking property"), which makes it possible to provide a stable flexographic printing plate with small variation in the size of the formed relief image.
[0131] When the photosensitive resin composition layer is cured by irradiation with ultraviolet light, the curing proceeds by radical polymerization. If oxygen is present during polymerization, the radical generating compound reacts with oxygen, suppressing the polymerization reaction. If the polymerization reaction is suppressed, the interface between the unexposed area that is removed in the development process and the exposed area that forms the pattern becomes unclear, so that even if the same design is drawn on a flexographic printing plate precursor, the size of the relief image may vary.
[0132] In contrast, if the intermediate layer blocks the diffusion of oxygen in the air into the photosensitive resin composition layer, thereby reducing the amount of oxygen present during UV curing, the polymerization reaction is less likely to be inhibited, and the interface between the unexposed area that is removed in the development step and the exposed area that forms the pattern becomes clear, thereby stabilizing the size of the relief image that is formed.
[0133] In addition, it is preferable that the diffusion barrier property and oxygen barrier property (hereinafter, collectively referred to simply as "barrier property") of the intermediate layer are stable regardless of the storage environment. One of the factors that can cause the barrier property to decrease is moisture absorption by the intermediate layer. When the intermediate layer absorbs moisture, the plasticity increases more than necessary, resulting in a decrease in the barrier property.
[0134] If the diffusion barrier property is reduced, the adhesiveness of the infrared ablation layer increases over time, and there is a risk that development residue from the infrared ablation layer may reattach to the plate during development. Also, if the oxygen barrier property is reduced, there is a risk that the amount of oxygen present increases when the relief image is cured with ultraviolet light, resulting in an unintended reduction in the size of the relief image.
[0135] In addition, the intermediate layer preferably exhibits the function of ensuring sufficient adhesion between the photosensitive resin composition layer and the infrared ablation layer, and has sufficient flexibility so as not to impair the flexibility of the flexographic printing original plate.
[0136] Since the adhesion between the photosensitive resin composition layer and the infrared ablation layer is sufficiently ensured, the cover film on the infrared ablation layer can be peeled off without damaging the infrared ablation layer in the manufacturing process of the flexographic printing plate. Also, since the infrared ablation layer and the intermediate layer are in close contact with each other in the development process, they can be removed simultaneously, so that the infrared ablation layer can be developed quickly.
[0137] The intermediate layer also has a function of protecting the infrared ablation layer. In the conventional manufacturing process of flexographic printing plates, when the infrared ablation layer is fed as a film, it may come into contact with a roll or may be rolled tightly during transport of the film roll, causing it to rub against the protective film and physically break off, resulting in pinholes. In addition, when the photosensitive resin composition layer and the infrared ablation layer are laminated by a method in which the photosensitive resin composition layer is coated on the infrared ablation layer while being extruded, pinholes may be generated due to friction generated when the heated and melted photosensitive resin composition flows on the infrared ablation layer.
[0138] In order to prevent the occurrence of such pinholes in the infrared ablation layer, it is preferable that the intermediate layer constituting the flexographic printing plate precursor of the first embodiment has physical strength and heat resistance (hereinafter collectively referred to as "PH resistance").
[0139] If there is a pinhole in the infrared ablation layer, the photosensitive resin composition layer in contact with the pinhole will be exposed during relief exposure, resulting in the formation of an unintended image and the problem of the relief image becoming larger than intended, resulting in poor reproducibility of the flexographic printing plate.
[0140] In the flexographic printing plate precursor of the first embodiment, the intermediate layer has an elongation to the breaking point of 5% to 200%, an elongation at the point where the stress is maximum of 3% to 200%, and a maximum stress value of 1.0 MPa to 15 MPa in a tensile stress-strain curve measured after molding into a No. 8 dumbbell shape with a thickness of 100 μm in accordance with JIS K 6251 (2017). This makes it possible to provide a flexographic printing plate precursor with good PH resistance that allows the infrared ablation layer and intermediate layer to be quickly removed during development and prevents scratches on the infrared ablation layer even after bending the plate.
[0141] In this embodiment, "a No. 8 dumbbell shape with a thickness of 100 μm" means a No. 8 dumbbell shape manufactured in accordance with JIS K 6251 (2017) except that the thickness is 100 μm.
[0142] 1.3.1. Description of tensile properties The tensile stress-strain curve diagram of this embodiment is a curve diagram in which the horizontal axis is strain (%) and the vertical axis is tensile stress (Pa), as shown in Figures 4 to 7. Detailed measurement methods are described in the Examples section.
[0143] In the present embodiment, the elongation to the break point of the intermediate layer is preferably small from the viewpoint of developability. This allows the intermediate layer to be brittle broken when stress is applied to the intermediate layer by a brush or spray in the development process, and the infrared ablation layer can be quickly removed as well. From this viewpoint, the elongation to the break point is 200% or less, more preferably 150% or less, even more preferably 100% or less, and particularly preferably 50% or less.
[0144] On the other hand, the elongation of the intermediate layer of the present embodiment up to the breaking point is preferably large from the viewpoint of suppressing PH during transportation and handling of the plate. From this viewpoint, the elongation up to the breaking point is 5% or more, preferably 7% or more, and more preferably 10% or more.
[0145] Up to the point where the stress of the intermediate layer is at its maximum, the intermediate layer is in an elastic region, and thus can be reversibly deformed. By being reversibly deformed, even if the master plate is curved, for example, when being wound around the drum of a laser drawing machine, damage to the infrared ablation layer caused by distortion between the intermediate layer and the infrared ablation layer can be suppressed. When a 3 mm thick master plate is wound around the smallest size laser drawing machine (CDI Spark 1712) generally available on the market, the surface of the master plate will elongate by about 2%. From this viewpoint, it is preferable that the elongation up to the point where the stress of the intermediate layer of this embodiment is at its maximum is large. Specifically, it is 3% or more, more preferably 5% or more, even more preferably 7% or more, and particularly preferably 10% or more.
[0146] On the other hand, the elongation at the point where the stress is maximum is preferably small from the viewpoint of developability. This allows the intermediate layer to be brittle broken when stress is applied to the intermediate layer by a brush or spray in the development process, and the infrared ablation layer can be quickly removed as well. From this viewpoint, the elongation at the point where the stress is maximum is 200% or less, more preferably 150% or less, even more preferably 100% or less, and particularly preferably 50% or less.
[0147] From the viewpoint of developability, it is preferable that the maximum stress value of the intermediate layer is small. This allows the infrared ablation layer and the intermediate layer to be quickly removed when stress is applied thereto by a brush, a spray, or the like during development. From this viewpoint, the maximum stress value is 15 MPa or less, preferably 13 MPa or more, and more preferably 10 MPa or more.
[0148] On the other hand, the maximum stress value of the intermediate layer is preferably large from the viewpoint of suppressing PH during transportation and handling of the plate. From this viewpoint, the maximum stress value is 1.0 MPa or more, preferably 2.0 MPa or more, more preferably 3.0 MPa or more, and even more preferably 4.0 MPa or more.
[0149] The point where the stress in the intermediate layer is at its maximum may be the same as the breaking point of the intermediate layer, as in Example 6 (FIG. 6) for example.
[0150] 1.3.2. Explanation of water contact angle In the intermediate layer of the first embodiment, the surface that interfaces with the infrared ablation layer preferably has a water contact angle of 60° or more 3 minutes after droplets are applied. This allows the intermediate layer to have low hygroscopicity and maintain high barrier properties even when stored under high humidity conditions. From this perspective, the water contact angle 3 minutes after droplets are applied is more preferably 65° or more, and even more preferably 70° or more.
[0151] In addition, the intermediate layer preferably has a water contact angle of 90° or less 3 minutes after deposition on the surface that is the interface with the infrared ablation layer. This allows the infrared ablation layer and the intermediate layer to be quickly removed during development. From this perspective, the water contact angle of 85° or less 3 minutes after deposition is more preferable, and 80° or less is even more preferable.
[0152] It is important to use the contact angle of the intermediate layer measured 3 minutes after the droplets landed on the surface. This can be an index for controlling the hydrophilicity of not only the surface of the intermediate layer but also the inside of the intermediate layer. The detailed measurement method is described in the Examples section.
[0153] The intermediate layer of the first embodiment preferably contains an emulsion compound (A) having a glass transition temperature (Tg) of 30° C. or higher. This makes it possible to adjust the tensile properties and water contact angle to predetermined numerical ranges, and provides a flexographic printing original plate in which the barrier properties of the intermediate layer do not decrease even when stored under high humidity conditions, and the infrared ablation layer and intermediate layer can be quickly removed during development.
[0154] Although the details are unclear, the inventors speculate as follows. First, by including the first characteristic "emulsion compound", the moisture resistance of the flexographic printing plate precursor can be improved. When the emulsion compound is applied and dried to form a thin film, the micelles break down and the hydrophobic parts appear on the surface. As a result, a hydrophobic intermediate layer can be formed whose barrier properties do not decrease even when stored under high humidity conditions.
[0155] Next, the second characteristic, "Tg of 30°C or more", does not decrease the barrier properties even when stored under high humidity conditions, and the infrared ablation layer and the intermediate layer can be quickly removed during development. Emulsion compound (A) with a Tg of 30°C or more is in a glassy state in which micro-Brownian motion is frozen at 0 to 30°C, which is the storage temperature of a typical flexographic printing plate. When water molecules in the air enter the flexographic printing plate, the water diffuses and enters using the micro-Brownian motion of the polymer that constitutes the plate as a driving force, but if the plate is in a glassy state, the water can be prevented from entering. This prevents the plasticity of the intermediate layer from increasing more than necessary due to moisture absorption, and the barrier properties can be maintained.
[0156] Furthermore, the emulsion compound (A) having a Tg of 30° C. or more is in a glassy state in which micro-Brownian motion is frozen at 30° C., which is the temperature in the development process of a general flexographic printing plate precursor. When the emulsion compound is in a glassy state, when a physical force is applied by a brush and / or a spray of a developer during development, the intermediate layer is broken brittlely, not ductilely. Brittle fracture is a phenomenon in which the deformation leading to fracture is small and the intermediate layer is broken quickly, compared to ductile fracture, and this allows the intermediate layer to be developed quickly. Furthermore, the infrared ablation layer laminated on the intermediate layer can also be removed at the same time.
[0157] In addition to the emulsion compound (A), the intermediate layer may contain, as necessary, an emulsion compound (B) having a glass transition temperature (Tg) of 10°C or less, an inorganic layer compound (C), a crosslinking agent (D), a binder polymer, a filler, a silicone oil, a surfactant, a coating aid, or the like.
[0158] The thickness of the intermediate layer of the flexographic printing plate precursor of the first embodiment is preferably thicker from the viewpoint of preventing material transfer between layers, and thinner from the viewpoint of developability. Taking these balances into consideration, the thickness of the intermediate layer is preferably more than 2.0 μm and 30 μm or less, more preferably more than 2.0 μm and 15 μm or less, and even more preferably 2.4 μm or more and 10 μm or less.
[0159] Furthermore, from the viewpoint of ease of the manufacturing process of the flexographic printing plate, it is preferable that the intermediate layer can be washed with the same developer as that of the infrared ablation layer and / or the photosensitive resin composition layer. If the intermediate layer has high washability, the time required for the washing process can be shortened, workability can be improved, and development of the photosensitive resin composition layer located below the intermediate layer can be easily performed.
[0160] Each component contained in the intermediate layer will be described in detail below.
[0161] 1.3.3. Emulsion Compound (A) The intermediate layer of the flexographic printing plate precursor of the first embodiment contains an emulsion compound (A) having a glass transition temperature (Tg) of 30° C. or higher. The term "emulsion compound" refers to a polymer having hydrophobic and hydrophilic parts in the molecule and dispersed in a micelle-like form in an aqueous solution.
[0162] The hydrophobic portion is not particularly limited, but examples thereof include saturated alkyl, unsaturated alkyl, polyether, polyester, poly(meth)acrylic, polyurethane, polycarbonate, polybutadiene, polystyrene, polyacrylonitrile, polychloroprene, polypropylene, polyisoprene, polyvinylidene chloride, polyvinyl chloride, polyamide, and copolymers of two or more polymers selected from these.
[0163] The hydrophilic portion is not particularly limited, but examples thereof include an amino group, an imino group, a tertiary amine group, a quaternary ammonium base, a hydrazide group, a carboxyl group, a sulfonyl group, a sulfate ester group, a phosphate ester group, an ether group, a hydroxyl group, an amide group, and atomic groups containing these, etc. These hydrophilic portions may be used alone or in combination of two or more kinds.
[0164] In particular, when development is carried out with an alkaline developer, it is preferable that the compound contains at least one of a carboxyl group and a sulfonyl group.
[0165] Specific emulsion compounds are not particularly limited, but examples thereof include water-dispersible latex polymers such as polyester emulsions, polyurethane emulsions, polyacrylamide emulsions, polybutadiene latex, natural rubber latex, styrene-butadiene copolymer latex, acrylonitrile-butadiene copolymer latex, polyvinylidene chloride latex, polychloroprene latex, polyisoprene latex, polyurethane latex, methyl methacrylate-butadiene copolymer latex, vinylpyridine polymer latex, butyl polymer latex, thiokol polymer latex, and acrylate polymer latex, and polymers obtained by copolymerizing these polymers with other components such as acrylic acid and methacrylic acid.
[0166] Among these, from the viewpoint of facilitating molecular design to increase Tg, it is preferable that the emulsion compound (A) contains an aromatic unit. In addition, when developed with an alkaline developer, from the viewpoint of rapid development, polyester emulsions are particularly preferable. The inventors speculate that this is because the ester bond is hydrolyzed by the alkali, allowing rapid removal during development.
[0167] The emulsion compound (A) may be used alone, but it is preferable to use two or more kinds in combination.
[0168] The polyester emulsion is a polymerization product of a polycarboxylic acid component and a glycol component. The polycarboxylic acid component is composed of one or more compounds selected from divalent or higher polycarboxylic acids and ester-forming derivatives of polycarboxylic acids. The ester-forming derivatives of polycarboxylic acids are derivatives of polycarboxylic acids such as anhydrides, esters, acid chlorides, and halides, which react with the glycol component described below to form esters. The polycarboxylic acid has two or more carboxyl groups per molecule.
[0169] Examples of the polycarboxylic acid component include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and dodecanedioic acid; and aromatic polycarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 5-sulfoisophthalic acid, 2-sulfoisophthalic acid, 4-sulfoisophthalic acid, sulfoterephthalic acid, 4-sulfonaphthalene-2,6-dicarboxylic acid, hemimellitic acid, trimellitic acid, trimesic acid, mellophanic acid, pyromellitic acid, benzenepentacarboxylic acid, mellitic acid, cyclopropane-1,2,3-tricarboxylic acid, cyclopentane-1,2,3,4-tetracarboxylic acid, and ethanetetracarboxylic acid.
[0170] Among these, as described above, from the viewpoint of facilitating molecular design for increasing Tg, it is preferable that the emulsion compound contains an aromatic unit, i.e., it is preferable that the polyester emulsion contains at least one aromatic polycarboxylic acid as a copolymerization component.
[0171] Furthermore, when it is desired to improve the developability in an alkaline developer, it is more preferable that the emulsion contains an aromatic polycarboxylic acid having a valence of three or more and / or an aromatic polycarboxylic acid having a metal sulfonate group, and a copolymerized polyester emulsion containing an aromatic polycarboxylic acid component as a copolymerization component and having a carboxyl group and / or a sulfonate group is more preferable.
[0172] The polyhydric alcohol is not particularly limited, but examples thereof include ethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, polytetramethylene glycol, polyhexamethylene glycol, polyheptamethylene glycol, polydecamethylene glycol, glycerin, trimethylolpropane, pentaerythritol, bisphenol A, bisphenol F, hydrogenated bisphenol A, hydrogenated bisphenol F, hydroquinone, naphthohydroquinone, anthrahydroquinone, 1,4-cyclohexanediol, tricyclodecanediol, tricyclodecane dimethanol, pentacyclopentadecanediol, and pentacyclopentadecanedimethanol. These may be used alone or in combination of two or more.
[0173] The ratio of the polyvalent carboxylic acid component to the polyhydric alcohol component is preferably adjusted so that the total number of carboxyl groups and their ester-forming derived groups contained in the polyvalent carboxylic acid component and the total number of hydroxyl groups and their ester-forming derived groups contained in the polyhydric alcohol component are in the range of 1:1.1 to 2.5 in terms of molar ratio. In this case, trivalent or higher polyvalent carboxylic acids are regarded as dicarboxylic acids to calculate the ratio.
[0174] The intermediate layer of the first embodiment preferably contains an emulsion compound (A) having a Tg of 30° C. or more. This makes it possible to provide a flexographic printing plate precursor having excellent developability and blocking properties for the reasons described above. From the viewpoint of expanding the applicable range of storage temperature and use temperature, it is preferable that the emulsion compound has a high Tg. On the other hand, from the viewpoint of film-forming properties, it is preferable that the emulsion compound is not in a glassy state during the coating and drying process when producing the intermediate layer.
[0175] From this viewpoint, the Tg of the emulsion compound (A) is preferably 30°C or higher, more preferably 35°C or higher and 120°C or lower, even more preferably 40°C or higher and 100°C or lower, and particularly preferably 45°C or higher and 70°C or lower.
[0176] The glass transition temperature Tg is a value measured by DSC in accordance with JIS K 7121 (1987). Specifically, an emulsion compound is placed in a differential scanning calorimeter, heated to (Tg+50°C) at a heating rate of 10°C / min, held for 10 minutes, and then rapidly cooled. The glass transition temperature (Tg) is read from the obtained differential thermal curve.
[0177] In addition, a commercially available product can be used as the emulsion compound (A). When the emulsion compound is a commercially available product, the Tg is preferentially adopted from the catalog data of the commercially available product.
[0178] From the viewpoint of developability, the acid value of the emulsion compound (A) contained in the intermediate layer is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, further preferably 20 mgKOH / g or more, and particularly preferably 30 mgKOH / g or more.
[0179] On the other hand, from the viewpoint of moisture absorption resistance, it is preferably 140 mgKOH / g or less, more preferably 120 mgKOH / g or less, even more preferably 100 mgKOH / g or less, and particularly preferably 80 mgKOH / g or less.
[0180] The number average molecular weight (Mn) of the emulsion compound (A) contained in the intermediate layer and having a Tg of 30° C. or more is preferably large from the viewpoint of increasing strength and preventing the occurrence of PH, and is preferably small from the viewpoint of prioritizing brittle fracture during development and enabling rapid removal. The inventors speculate that this is because, as disclosed in the literature "Polymer, 37, 1177 (1996)", the smaller the number average molecular weight, the easier it is to form crazes, which are a precursor phenomenon of brittle fracture.
[0181] Considering these balances, the number average molecular weight Mn of the emulsion compound (A) is preferably 1,000 or more and 100,000 or less, more preferably 1,500 or more and 75,000 or less, further preferably 2,000 or more and 50,000 or less, and particularly preferably 2,500 or more and 30,000 or less.
[0182] The number average molecular weight Mn can be determined by measuring the molecular weight of the peak of the chromatogram using a calibration curve (created using the peak molecular weight of the standard polystyrene) obtained by measuring a commercially available standard polystyrene. The details of the measurement conditions are as described in the Examples section below. In addition, when the emulsion compound is a commercially available product, the catalog data of the commercially available product is used as the number average molecular weight.
[0183] The content of the emulsion compound (A) is preferably high from the viewpoint of developability, plate reproducibility, and adhesion of development residue, and is preferably low from the viewpoint of improving the elongation of the intermediate layer and suppressing PH during handling. From this viewpoint, the content of the emulsion compound (A) is preferably 10% by mass or more, more preferably 25% by mass or more, and particularly preferably 40% by mass or more, based on the total amount of the intermediate layer. In addition, the upper limit of the content of the emulsion compound (A) is not particularly limited, but is preferably 99% by mass or less, more preferably 98% by mass or less, more preferably 95% by mass or less, and particularly preferably 80% by mass or less, based on the total amount of the intermediate layer. By having the content of the emulsion compound (A) of 10% by mass or more, the developability and plate reproducibility tend to be further improved, and the adhesion of development residue tends to be further reduced.
[0184] The particle size of the emulsion compound (A) can be selected from any range. A small particle size allows for rapid development, while a large particle size increases the dispersion stability in the coating liquid. Considering the balance between these two, the particle size of the emulsion compound (A) is preferably 5 nm or more and 1000 nm or less, and more preferably 10 nm or more and 500 nm or less.
[0185] When dispersing the emulsion compound (A) in water, a small amount of an alkaline compound may be added in addition to water, which tends to improve the dispersibility of the emulsion compound (A) and improve plate reproducibility.
[0186] Examples of the alkaline compound include, but are not limited to, ammonia, monoethanolamine, diethanolamine, triethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, monoethylamine, diethylamine, triethylamine, butylamine, pentylamine, propylamine, isopropylamine, benzylamine, sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, sodium percarbonate, sodium hydrogencarbonate, potassium carbonate, calcium carbonate, etc. Among these, from the viewpoints of safety and basicity, ammonia, diethanolamine, triethanolamine, sodium hydroxide, potassium hydroxide, and sodium peroxy acid are preferred.
[0187] The amount added is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and particularly preferably 2 parts by mass or less, based on 100 parts by mass of the emulsion compound (A).
[0188] 1.3.4. Emulsion Compound (B) In addition to the emulsion compound (A), the intermediate layer of the first embodiment preferably contains an emulsion compound (B) having a Tg of 10° C. or less in order to provide sufficient flexibility so as not to impair the flexibility of the flexographic printing plate precursor.
[0189] The present inventors speculate that the Tg of the emulsion compound (B) is lower than the general use temperature of 20° C. of a flexographic printing plate precursor, and thus the emulsion compound (B) undergoes micro-Brownian motion, thereby ensuring sufficient flexibility. From this viewpoint, the Tg of the emulsion compound (B) is preferably 10° C. or lower, and more preferably 0° C. or lower.
[0190] Specific emulsion compound (B) is not particularly limited as long as its Tg is 10° C. or less, and examples of the type include the same as those of emulsion compound (A) above. Specific examples include water-dispersible latex polymers such as polyester emulsion, polyurethane emulsion, polyacrylamide emulsion, polybutadiene latex, natural rubber latex, styrene-butadiene copolymer latex, acrylonitrile-butadiene copolymer latex, polyvinylidene chloride latex, polychloroprene latex, polyisoprene latex, polyurethane latex, methyl methacrylate-butadiene copolymer latex, vinylpyridine polymer latex, butyl polymer latex, thiokol polymer latex, and acrylate polymer latex, and polymers obtained by copolymerizing these polymers with other components such as acrylic acid and methacrylic acid.
[0191] Among these, polyurethane emulsion, polybutadiene latex, styrene-butadiene copolymer latex, and acrylonitrile-butadiene copolymer latex are particularly preferred from the viewpoint of flexibility and compatibility with polyester emulsion. By selecting these emulsions, the elongation of the intermediate layer can be increased, and it becomes easy to adjust the tensile properties to a predetermined numerical range. These emulsions may contain small amounts of optional components such as (meth)acrylic acid and antioxidants as copolymerization components or additives.
[0192] The content of the emulsion compound (B) is preferably 5% by mass or more and 90% by mass or less, more preferably 10% by mass or more and 70% by mass or less, and particularly preferably 15% by mass or more and 40% by mass or less, based on the total amount of the intermediate layer. When the content of the emulsion compound (B) is 5% by mass or more, the flexibility of the flexographic printing plate precursor tends to be sufficient so as not to impair the flexibility. In addition, when the content of the emulsion compound (B) is 90% by mass or less, the developability tends to be further improved.
[0193] The particle size of the emulsion compound (B) can be selected from any range. A small particle size allows for rapid development, while a large particle size increases the dispersion stability in the coating liquid. Considering the balance between these two, the particle size of the emulsion compound (B) is preferably 5 nm or more and 1000 nm or less, and more preferably 10 nm or more and 500 nm or less.
[0194] The weight ratio (A) / (B) of the emulsion compound (A) to the emulsion compound (B) is preferably 1.0 or more and 2.3 or less, more preferably 1.1 or more and 2.0 or less. When the weight ratio (A) / (B) of the emulsion compound (A) to the emulsion compound (B) is 1.0 or more, the flexographic printing plate has sufficient flexibility so as not to impair the flexibility of the flexographic printing plate precursor, and the PH resistance tends to be good. In addition, when the weight ratio (A) / (B) of the emulsion compound (A) to the emulsion compound (B) is 2.3 or less, the elongation at break is kept low, and plastic fracture occurs preferentially during development, and the developability tends to be further improved.
[0195] 1.3.5. Inorganic layered compounds (C) In the first embodiment, the term "inorganic layered compound (C)" refers to an inorganic compound in which unit crystal layers are overlapped to form one layered particle. As the inorganic layered compound (C), a compound that swells and / or cleaves in water is preferred, and examples thereof include clay compounds that swell in water. In addition, as the inorganic layered compound (C), those containing aluminum hydroxide, aluminum oxide, barium sulfate, and potassium titanate are also included, so long as they satisfy the above definition of the inorganic layered compound. Among these compounds, particularly preferred are clay compounds that swell in water, and those containing aluminum hydroxide or aluminum oxide.
[0196] Such clay compounds are not particularly limited, but include, for example, Si 4+ O 2- The layers are coordinated to form a tetrahedral structure, and the Al 3+ , Mg 2+ , Fe 2+ , Fe 3+Etc., O 2- and OH - The clay compounds may be either natural or synthetic compounds, and may be compounds in which the layers that form the octahedral structure are bonded to each other in a 1:1 or 2:1 ratio to form a layered structure.
[0197] Aluminum hydroxide or aluminum oxide may be dispersed in water in the form of fine particles. This may be a compound prepared by subjecting various hydrated aluminum hydroxides (amorphous aluminum hydroxide, gibbsite, bialite, boehmite, diaspore) to hydrolysis and dehydration polycondensation in a solution to disperse metal oxide or metal hydroxide in a sol state, or may be a compound prepared by reacting aluminum hydroxide with water under high temperature and high pressure conditions using a hydrothermal synthesis method and then dispersing the resulting product in water.
[0198] From the viewpoints of compatibility with the emulsion compound and the aforementioned developability, the inorganic layered compound (C) is preferably a water-swellable clay mineral that swells in water or dissociates into layers, and more preferably disperses in water in the form of a single layer or multiple layers.
[0199] Preferred clay minerals are not particularly limited, but examples thereof include layered silicate minerals such as kaolinite, dickite, halloysite, talc, pyrophyllite, saponite, hectorite, montmorillonite, beidellite, vermiculite, mica, and paragonite.
[0200] In particular, mica is preferred as the inorganic layered compound (C) since it has a high aspect ratio compared to other inorganic layered compounds (C), and therefore the labyrinth effect works more effectively, and the blocking properties formed in combination with the emulsion compound are particularly high. Water-swellable synthetic mica is more preferred since the intermediate layer in which the inorganic layered compound is uniformly dispersed has a narrow average particle size distribution and therefore has high developability.
[0201] The size of the inorganic layered compound (C) is preferably such that the inorganic layered compound (C) is uniformly arranged in the intermediate layer formed together with the emulsion compound, the labyrinth effect works more effectively, and the barrier property is particularly high.
[0202] From this viewpoint, the inorganic layered compound (C) preferably has an average particle size of 10 μm or less and a thickness of 500 nm or less, and more preferably has an average particle size of 10 μm or less and a thickness of 100 nm or less.
[0203] When the average particle size is 1 μm or more, the intermediate layer can exhibit sufficient blocking properties, and when the average particle size is 10 μm or less, the occurrence of unevenness in appearance can be prevented. A thickness of 10 nm or more allows the particles to maintain their shape, making it suitable for practical use, while a thickness of 500 nm or less allows for uniform coating and provides sufficient barrier properties.
[0204] Examples of commercially available inorganic layered compounds (C) include, but are not limited to, micromica (synthetic mica), Somasif (registered trademark of Katakura Co-op Agri Co., Ltd., synthetic mica), Kunipia (registered trademark of Kunimine Kogyo Co., Ltd., montmorillonite), Sumecton (registered trademark of Kunimine Kogyo Co., Ltd.) SA (synthetic saponite) manufactured by Kunimine Kogyo Co., Ltd., Bengel (registered trademark of Hojun Co., Ltd., refined natural bentonite) manufactured by Hojun Co., Ltd., Aluminosol F-1000, F-3000, 5N, and 10N manufactured by Kawaken Fine Chemical Co., Ltd., plate-shaped alumina powder Seraph 00610, 02025, 02050, 05025, 05070, 07070, and 10030 manufactured by Kinsei Matec Co., Ltd., and Tismo D and Tismo N manufactured by Otsuka Chemical Co., Ltd.
[0205] In the intermediate layer of the first embodiment, the higher the content of the inorganic layered compound (C), the more improved the barrier properties and developability. On the other hand, the lower the content of the inorganic layered compound (C), the more improved the film-forming properties and the easier it is to obtain a film with a uniform thickness. Considering the balance between these, the content of the inorganic layered compound (C) is preferably 0.1% by mass or more and 20% by mass or less, more preferably 0.5% by mass or more and 10% by mass or less, and even more preferably 1% by mass or more and 5% by mass or less, based on the total amount of the intermediate layer.
[0206] 1.3.6. Crosslinking Agent (D) In the flexographic printing plate precursor of the first embodiment, the intermediate layer preferably contains a crosslinking agent (D). This crosslinks the emulsion compound, further increasing Tg, making the intermediate layer more susceptible to brittle fracture during development, and allowing for rapid development. Furthermore, the strength of the intermediate layer can be increased, and the PH resistance can be improved.
[0207] The crosslinking agent (D) is not particularly limited as long as it can form a crosslinked structure with the above-mentioned emulsion compound (A) and / or (B). Such crosslinking agents are not particularly limited, but include, for example, carbodiimide-based crosslinking agents; epoxy-based crosslinking agents; oxazoline-based crosslinking agents; ethyleneimine-based crosslinking agents; polyfunctional isocyanate-based crosslinking agents such as tolylene diisocyanate, trimethylolpropane tolylene diisocyanate, and diphenylmethane triisocyanate; metal salt-based crosslinking agents; metal chelate-based crosslinking agents; peroxide-based crosslinking agents; melamine resins; and phenolic resins. The reactive groups of these crosslinking agents may be modified with protective groups from the viewpoint of storage stability.
[0208] In the step of applying the coating liquid used to form the intermediate layer to the infrared ablation layer described later, the crosslinking agent (D) is preferably present in the coating liquid without crosslinking and is chemically stable, and is preferably crosslinked by heat during drying after application. From the above viewpoint, a carbodiimide-based crosslinking agent or a polyfunctional isocyanate-based crosslinking agent is preferably used, and in particular, a compound having two or more carbodiimide groups in one molecule is more preferably used.
[0209] In addition, commercially available products may be used as these crosslinking agents. Examples of commercially available carbodiimide crosslinking agents include, but are not limited to, "DICNAL (registered trademark) HX" manufactured by DIC Corporation and "Carbodilite (registered trademark)" manufactured by Nisshinbo Chemical Co., Ltd. In addition, examples of commercially available isocyanate compounds include blocked isocyanate SU-268A, Meikanate CX, DM-6400, and Meikanate TP-10 (manufactured by Meisei Chemical Industry Co., Ltd.).
[0210] The content of the thermal crosslinking agent (D) is preferably 0.5% by mass to 15% by mass, more preferably 1% by mass to 10% by mass, and more preferably 2% by mass to 7% by mass, based on the total amount of the intermediate layer. By having the content of the crosslinking agent within the above range, the developability is good and the PH resistance is improved.
[0211] 1.3.7. Binder polymer (E) In the flexographic printing plate precursor of the first embodiment, the intermediate layer may contain a binder polymer (E) in addition to the emulsion compounds (A) and (B). The binder polymer is distinguished from the emulsion compounds (A) and (B) in that it is not dispersed / dissolved in water or is completely dissolved in water.
[0212] The binder polymer (E) is not particularly limited, but examples thereof include polymers such as ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyvinyl acetate, polyvinyl butyral, polyvinylpyrrolidone, polyvinyl chloride, polyvinylidene chloride, polyvinyl fluoride, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyacetal, polycarbonate, polystyrene, polycarbonate, polyethylene, polypropylene, cellulose derivatives, polyester, polyamide, polyimide, polyurethane, silicone rubber, butyl rubber, and isoprene rubber, and copolymers thereof.
[0213] These binder polymers (E) may be used alone or in combination of two or more.
[0214] Among these binder polymers (E), a binder polymer that is completely soluble in water is preferred from the viewpoint of improving developability when developing with an aqueous developer, whereas a binder polymer that is not dispersible / soluble in water is preferred when improving moisture resistance.
[0215] Of the above, polyamide is preferred. The polyamide is not particularly limited as long as it is a polymer having a polyamide bond, and examples thereof include lactams having 4 to 40 carbon atoms, aminocarboxylic acids, and equimolar salts of diamines and dicarboxylic acids.
[0216] As the polymer having a polyamide bond, a conventionally known soluble synthetic polymer compound can be used. For example, polyetheramide (for example, see JP-A-55-79437, etc.), polyetheresteramide (for example, see JP-A-58-113537, etc.), tertiary nitrogen-containing polyamide (for example, see JP-A-50-76055, etc.), ammonium salt-type tertiary nitrogen atom-containing polyamide (for example, see JP-A-53-36555, etc.), addition polymer of amide compound having one or more amide bonds and organic diisocyanate compound (for example, see JP-A-58-140737, etc.), addition polymer of diamine having no amide bond and organic diisocyanate compound (for example, see JP-A-4-97154, etc.), etc. can be mentioned. These water-soluble polyamides may be used alone or in combination of two or more kinds.
[0217] Among polyamides, water-soluble polyamides consisting of copolymers of amine compounds and / or alkylene oxide compounds with caprolactam are preferred. It is possible to provide an intermediate layer with improved moisture resistance while maintaining the barrier properties and developability that are advantages of water-soluble polyamides. The inventors speculate that this is because the amine groups or alkylene oxide units are highly compatible with the hydrophilic portion of the emulsion compound (A), improving the dispersibility of the emulsion compound (A), thereby exerting a high effect.
[0218] The polyamide resin consisting of a copolymer of an amine compound and / or an alkylene oxide compound with caprolactam may be synthesized by a known method exemplified in JP-A-55-79437, or a commercially available product may be used. An example of a commercially available polyamide resin is "AQ Nylon (registered trademark)" manufactured by Toray Industries, Inc.
[0219] When the intermediate layer contains the binder polymer (E), its content can be set arbitrarily within a range that does not impair the effects of the present invention. If the amount of the binder polymer added is large, the blocking property and adhesion tend to be improved, but the developability and flexibility tend to be reduced. Considering the balance between these, the content of the binder polymer (E) is preferably 5% by mass to 70% by mass or less, more preferably 10% by mass to 50% by mass, based on the total amount of the intermediate layer.
[0220] 1.3.8. Silicone compounds (F) The intermediate layer can be formed, for example, by coating on the infrared ablation layer. In order to uniformly coat the intermediate layer on the infrared ablation layer, it is preferable that the intermediate layer contains a silicone compound (F) from the viewpoint of controlling the surface energy.
[0221] The silicone compound (F) is not particularly limited, but examples of preferred compounds include compounds having polyalkylsiloxanes in the main chain, such as polydimethylsiloxane and polydiethylsiloxane. Alternatively, the silicone compound (F) may be a compound having a polysiloxane structure in a part of the molecule.
[0222] Furthermore, a compound having a specific organic group introduced into a polysiloxane structure can also be used. Specifically, a compound having an organic group introduced into a side chain of a polysiloxane, a compound having an organic group introduced into both ends of a polysiloxane, a compound having an organic group introduced into one end of a polysiloxane, a compound having an organic group introduced into both a side chain and an end of a polysiloxane, etc. can be used. From the viewpoint of ensuring the adhesion between the intermediate layer and the photosensitive resin composition layer, it is preferable to use a silicone compound having an organic group introduced into it.
[0223] The organic group to be introduced into the polysiloxane structure is not particularly limited, but examples thereof include an amino group, a carboxyl group, a carbinol group, an aryl group, an alkyl group, an alkoxycarbonyl group, an alkoxy group, a linear or branched alkyl group substituted with at least one aryl group, and a polyoxyalkylene group (hereinafter also referred to as a "polyether group").
[0224] The silicone compound (F) is not particularly limited, but for example, various organic group-substituted silicone oils manufactured by Shin-Etsu Chemical Co., Ltd., Wacker Asahi Kasei Silicones Co., Ltd., GE Toshiba Silicones Co., Ltd., and Dow Corning Toray Silicones Co., Ltd. can be used.
[0225] The content of the silicone compound (F) is preferably from 0.01 to 10% by mass, more preferably from 0.5 to 8.0% by mass, and even more preferably from 1.0 to 6.0% by mass, based on the total amount of the intermediate layer.
[0226] Surfactants The intermediate layer can be formed, for example, by coating on the infrared ablation layer. In order to uniformly coat the intermediate layer on the infrared ablation layer, the intermediate layer preferably contains a surfactant from the viewpoint of controlling the surface energy.
[0227] The surfactant is not particularly limited, but examples thereof include anionic surfactants, ionic surfactants, nonionic surfactants, anionic reactive surfactants, nonionic reactive surfactants, etc. The surfactants may be used alone or in combination of two or more kinds.
[0228] The anionic surfactant is not particularly limited, but examples thereof include sodium polyoxyethylene styrenated phenyl ether sulfate, sodium polyoxyalkylene branched decyl ether sulfate, ammonium polyoxyethylene isodecyl ether sulfate, sodium polyoxyethylene tridecyl ether sulfate, sodium polyoxyethylene alkyl (C8-C20) ether sulfate, ammonium polyoxyethylene oleyl cetyl ether sulfate, sodium polyoxyethylene oleyl cetyl ether sulfate, polyoxyethylene tridecyl ether phosphate, polyoxyethylene alkyl (C2-C16) ether phosphate, polyoxyethylene oleyl cetyl ... Examples include ethylene alkyl (C2-C16) ether phosphate monoethanolamine salt, sodium alkyl (C2-C16) phosphate, alkyl (C2-C16) phosphate monoethanolamine salt, disodium lauryl sulfosuccinate, disodium lauryl polyoxyethylene sulfosuccinate, disodium polyoxyethylene alkyl (C2-C20) sulfosuccinate, sodium linear alkylbenzene sulfonate, linear alkylbenzene sulfonic acid, sodium alpha-olefin sulfonate, phenol sulfonic acid, sodium dioctyl sulfosuccinate, sodium lauryl sulfate, and potassium salts of higher fatty acids.
[0229] The ionic surfactant is not particularly limited, but examples thereof include ionic surfactants such as alkyl (C8-C20) trimethyl ammonium chloride, alkyl (C8-C20) dimethyl ethyl ammonium chloride, didecyl dimethyl ammonium chloride, lauryl dimethyl benzyl ammonium chloride, stearyl dimethyl hydroxyethyl ammonium paratoluenesulfonate, stearyl dimethyl aminopropyl amide, tributyl benzyl ammonium chloride, lauryl dimethyl amino acetate betaine, lauric acid amidopropyl betaine, coconut oil fatty acid amidopropyl betaine, octanoic acid amidopropyl betaine, and lauryl dimethyl amine oxide.
[0230] The nonionic surfactant is not particularly limited, but examples thereof include polyoxyalkylene tridecyl ether, polyoxyethylene isodecyl ether, polyoxyalkylene lauryl ether, polyoxyalkylene alkyl ether, a mixture of polyoxyalkylene ether and polyether polyol, polyether polyol, polyoxyethylene sulfonated phenyl ether, polyoxyethylene naphthyl ether, phenoxyethanol, polyoxyethylene phenyl ether, polyoxyethylene polyoxypropylene glycol, polyoxyethylene lauryl ether, polyoxyethylene oleyl cetyl ether, and polyoxyethylene oleic acid ethyl ether. Examples of nonionic surfactants include sucrose ester, polyoxyethylene distearate ester, polyoxyethylene glyceryl isostearate, polyoxyethylene hydrogenated castor oil, coconut oil fatty acid diethanolamide, polyoxyethylene alkylamine, sorbitan trioleate, sorbitan sesquioleate, sorbitan monooleate, sorbitan monococolate, sorbitan monocaprate, polyoxyethylene sorbitan monococoate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, octyl polyglycoside, butyl polyglycoside, sucrose benzoate, sucrose acetate, and sucrose fatty acid ester.
[0231] The anionic reactive surfactant is not particularly limited, but examples thereof include anionic reactive surfactants such as polyoxyethylene-1-(allyloxymethyl) alkyl ether ammonium sulfate and polyoxyethylene nonylpropenyl phenyl ether ammonium sulfate.
[0232] The nonionic reactive surfactant is not particularly limited, but examples thereof include nonionic reactive surfactants such as polyoxyethylene nonylpropenyl phenyl ether.
[0233] The surfactant may be added to the intermediate layer as well as other layers, such as the photosensitive resin composition layer. When the total amount of the material of the layer to which the surfactant is added is taken as 100% by mass, the content of the surfactant is preferably 0.1% by mass or more and 5.0% by mass or less, more preferably 0.5% by mass or more and 3.0% by mass or less, and even more preferably 0.5% by mass or more and 2.0% by mass or less. By containing 0.1% by mass or more of the surfactant, the washing speed during development after exposure can be improved. In addition, by containing 5.0% by mass or less of the surfactant, swelling of the flexographic printing plate precursor tends to be suppressed.
[0234] 1.4.Infrared ablation layer The flexographic printing plate precursor of the first embodiment has an infrared ablation layer on an intermediate layer. The infrared ablation layer can be patterned by infrared rays and serves as a mask image when the photosensitive resin composition layer is exposed and cured. When the unexposed parts of the photosensitive resin composition layer are washed out after the exposure, the infrared ablation layer is also removed at the same time.
[0235] The infrared ablation layer is preferably composed of a binder polymer and an infrared absorbing agent.
[0236] The binder polymer is not particularly limited, but examples thereof include polyamide, polyester, and copolymers of monovinyl-substituted aromatic hydrocarbons and conjugated dienes. In particular, copolymers of monovinyl-substituted aromatic hydrocarbons such as styrene, α-methylstyrene, and vinyltoluene and conjugated dienes such as 1,3-butadiene and isoprene are preferred. By using such a binder polymer to form the infrared ablation layer, the affinity with the intermediate layer is high and the adhesion is good.
[0237] The thickness of the infrared ablation layer of the flexographic printing plate precursor of the first embodiment is preferably thicker from the viewpoint of ensuring light shielding against ultraviolet rays during the step of exposing the flexographic printing plate precursor, and is preferably thinner from the viewpoint of improving developability. From these viewpoints, the thickness of the infrared ablation layer is preferably 0.1 μm or more and 20 μm or less, more preferably 0.5 μm or more and 15 μm or less, and even more preferably 1.0 μm or more and 10 μm or less.
[0238] As for the non-infrared shielding effect of the infrared ablation layer, the optical density of the infrared ablation layer is preferably 2 or more, and more preferably 3 or more. The optical density can be measured using a D200-II transmission densitometer (manufactured by GretagMacbeth). The optical density is what is called visual perception (ISO visual), and the light to be measured is in the wavelength region of about 400 to 750 nm.
[0239] As the infrared absorbing agent, a simple substance or a compound having strong absorption characteristics in the wavelength range of 750 nm to 20,000 nm is usually used. It is preferable that the infrared absorbing agent also serves as a non-infrared shielding material, but the infrared absorbing agent and the non-infrared shielding material may be added separately.
[0240] The infrared absorbing agent is preferably one that has high absorption in the infrared region and can be uniformly dispersed in the infrared ablation layer. Examples of such substances include, but are not limited to, inorganic pigments such as carbon black, graphite, iron oxide, chromium oxide, and copper chromite, and dyes such as phthalocyanine and substituted phthalocyanine derivatives, cyanine dyes, merocyanine dyes, polymethine dyes, and metal thiolate dyes.
[0241] As the non-infrared shielding material, a material that reflects or absorbs ultraviolet light can be used. Although not particularly limited, suitable examples include carbon black, ultraviolet absorbers, graphite, etc.
[0242] The infrared absorbing agent and the non-infrared shielding material may be used alone or in combination of two or more.
[0243] As the infrared absorbing agent, carbon black is particularly preferred because it also has a non-infrared shielding effect, is easily available, and is inexpensive. The particle size of carbon black can be selected within any range, but generally, the smaller the particle size, the higher the sensitivity to infrared rays and the worse the dispersibility. From the above viewpoints, the particle size of carbon black is preferably 13 nm or more and 80 nm or less, more preferably 15 nm or more and 70 nm or less, and even more preferably 18 nm or more and 60 nm or less.
[0244] Carbon black is not particularly limited, but is classified into, for example, furnace black, channel black, thermal black, acetylene black, lamp black, etc., depending on the production method. Furnace black is preferred from the viewpoints of availability and versatility.
[0245] The infrared ablation layer may contain a dispersant to assist the dispersion of carbon black. The dispersant is not particularly limited, but is preferably, for example, a compound having an adsorption portion capable of interacting with the surface functional group of the infrared absorbing agent and a resin-compatible portion capable of being compatible with the resin.
[0246] The adsorption moiety of the dispersant is not particularly limited, but examples thereof include amino groups, amide groups, urethane groups, carboxyl groups, carbonyl groups, sulfone groups, and nitro groups, with amino groups, amide groups, and urethane groups being preferred.
[0247] The resin compatible portion is not particularly limited, but examples thereof include saturated alkyl, unsaturated alkyl, polyether, polyester, poly(meth)acrylic, and polyol.
[0248] 2. Second embodiment: Flexographic printing plate The flexographic printing plate precursor of the second embodiment comprises a support, and on the support, a photosensitive resin composition layer, an intermediate layer, and an infrared ablation layer, in that order, and the intermediate layer has a water contact angle of 70° or more and 90° or less at the interface with the infrared ablation layer, 3 minutes after landing.
[0249] In the second embodiment, the configuration exemplified in the first embodiment can be similarly exemplified, except that the water contact angle on the intermediate layer surface 3 minutes after landing at the interface between the intermediate layer and the infrared ablation layer is 70° or more and 90° or less.
[0250] For example, the support, the photosensitive resin composition layer, and the infrared ablation layer may be the same as those in the first embodiment. In addition, the intermediate layer may be configured in the same manner as in the first embodiment as long as the water contact angle is satisfied. For example, the components and compositions used in the intermediate layer may be the same. In addition, the same values may be given for physical properties such as water contact angle and tensile properties, and the first embodiment may be referred to for the measurement method and adjustment method.
[0251] 3. Manufacturing method of flexographic printing plate The flexographic printing plate precursor of the present embodiment can be produced by various methods without any particular limitation as long as the photosensitive resin composition layer, the intermediate layer, and the infrared ablation layer are laminated on the support. Specifically, the following methods can be mentioned.
[0252] First, the raw materials of the photosensitive resin composition that is the material of the photosensitive resin composition layer are dissolved and mixed in an appropriate solvent, for example, chloroform, tetrachloroethylene, methyl ethyl ketone, toluene, etc., and cast into a mold frame to evaporate the solvent to form a plate, or a photosensitive resin composition layer is obtained by kneading the raw materials in a kneader, roll mill, or screw extruder without using a solvent, and then molding to a desired thickness using a calendar roll, press, etc., and a support is laminated to this to obtain a laminate of the support and the photosensitive resin composition layer.
[0253] Next, an intermediate layer and an infrared ablation layer are formed on the photosensitive resin composition layer. In order to provide the intermediate layer and the infrared ablation layer on the surface of the photosensitive resin composition layer, for example, the components constituting the intermediate layer and the components constituting the infrared ablation layer are dispersed or dissolved in a suitable solvent by forced stirring or ultrasonic stirring with a stirring blade, or are pre-kneaded using an extruder or kneader and then dispersed or dissolved in a suitable solvent to obtain a predetermined dispersion or solution, and then the dispersion or solution is directly coated on the photosensitive resin composition layer to form the intermediate layer and the infrared ablation layer.
[0254] In addition, a cover sheet made of, for example, polyester, polypropylene or the like may be provided on the infrared ablation layer.
[0255] In another method, a material constituting the infrared ablation layer is coated on a specified cover sheet to obtain a film having an infrared ablation layer, and then a material constituting the intermediate layer is coated on the infrared ablation layer to obtain a cover film having the infrared ablation layer and the intermediate layer laminated on the cover sheet, and then this cover film is laminated or press-bonded to the photosensitive resin composition layer forming surface side of the laminate of the support and the photosensitive resin composition layer, thereby forming an intermediate layer and an infrared ablation layer on the photosensitive resin composition layer.
[0256] After the photosensitive resin composition layer is formed into a sheet, the cover film or support is usually adhered to the photosensitive resin composition layer by roll lamination, and after lamination, hot pressing can be performed to obtain a flexographic printing original plate with even better thickness accuracy.
[0257] 4. How flexographic printing plates are manufactured A method for producing a flexographic printing plate of this embodiment includes a back exposure step of irradiating the flexographic printing original plate with ultraviolet light from the support side, an infrared irradiation step of irradiating the infrared ablation layer with infrared light to draw and process a pattern, an exposure step of irradiating the photosensitive resin composition layer with ultraviolet light through the intermediate layer using the infrared ablation layer on which the pattern has been drawn and processed as a mask to selectively expose the photosensitive resin composition layer, and a development step of removing unexposed areas of the infrared ablation layer, the intermediate layer, and the photosensitive resin composition layer.
[0258] Thereafter, a post-exposure treatment step is carried out as necessary, to obtain a flexographic printing plate (relief printing plate) made of a cured product of the photosensitive resin composition layer. From the viewpoint of imparting releasability, the surface of the printing plate may be brought into contact with a liquid containing a silicone compound and / or a fluorine compound.
[0259] A schematic diagram showing a method for producing a flexographic printing plate using a flexographic printing plate precursor of this embodiment is shown in Figure 2. Each step will be described in detail below.
[0260] 4.1. Back exposure process First, in the back exposure step S1, the entire surface of the flexographic printing original plate 10 is exposed to ultraviolet light through the support 11 (back exposure) to harden the photosensitive resin composition layer 12 into a thin, uniform hardened layer. The exposure method at this time is not particularly limited, and can be performed using a known irradiation unit.
[0261] The ultraviolet light to be used may have a wavelength of 150 to 500 nm, and preferably has a wavelength of 300 to 400 nm.
[0262] The light source of ultraviolet light is not particularly limited, but may be, for example, a low pressure mercury lamp, a high pressure mercury lamp, an extra-high pressure mercury lamp, a metal halide lamp, a xenon lamp, a zirconium lamp, a carbon arc lamp, an ultraviolet fluorescent lamp, an LED lamp, etc. Ultraviolet light exposure units are commercially available, and for example, AFP 1216 EHQ (manufactured by Asahi Kasei Corporation) or XPS Crystal (manufactured by Esko Graphic Co., Ltd.) may be used.
[0263] The back exposure step may be performed before the infrared irradiation step, or may be performed simultaneously with the back exposure step S1 and the patterning step S3 as shown in Fig. 3. The process in Fig. 3 is the same as that shown in Fig. 2 except for the order of the steps.
[0264] 4.2. Infrared irradiation process Next, in the infrared irradiation step S2, the infrared ablation layer 14 is laser-drawn, i.e., laser-ablated, to produce a negative pattern 14a. If the flexographic printing original plate 10 has a cover film on the infrared ablation layer 14, the cover film is first peeled off before infrared irradiation. Then, the infrared ablation layer is irradiated with infrared rays in a pattern to form a mask on the photosensitive resin composition layer.
[0265] Suitable infrared lasers include, for example, ND / YAG lasers (e.g., 1064 nm) or diode lasers (e.g., 830 nm). Laser systems suitable for the CTP platemaking technology are commercially available, and for example, a diode laser system CDI Spark (ESKO GRAPHICS) can be used. This laser system includes a rotating cylindrical drum that holds a flexographic printing original plate, an IR laser irradiation device, and a layout computer, and image information is directly transmitted from the layout computer to the laser device.
[0266] 4.3.Exposure process In the exposure process S3, the infrared ablation layer 14a on which a negative pattern is formed is used as a mask to perform image exposure (relief exposure) on the photosensitive resin composition layer 12 through the intermediate layer 13, thereby forming a cured photosensitive resin composition layer 12a.
[0267] At this time, the light passing through the mask promotes the curing reaction of the photosensitive resin composition layer, and the pattern formed on the infrared ablation layer is transferred to the photosensitive resin composition layer with the concaves and convexes reversed. Note that the entire surface of the flexographic printing plate may be irradiated with ultraviolet light.
[0268] The exposure step can be carried out with the plate attached to the laser cylinder, but more commonly the plate is removed from the laser device and irradiated using a conventional irradiation unit, which can be the same as that used for UV irradiation from the support side.
[0269] When the flexographic printing plate precursor of this embodiment has an intermediate layer such as an oxygen inhibition layer or an adhesive layer, and the amount of ultraviolet light absorbed by the intermediate layer as an oxygen inhibition layer is large and cannot be ignored in the exposure process, it is preferable to appropriately adjust the amount of ultraviolet light irradiation taking into account in advance the amount of ultraviolet light absorbed by the intermediate layer as an oxygen inhibition layer.
[0270] 4.4.Developing process Next, a development step is performed. In the development step, the infrared ablation layer 14a, the intermediate layer 13, and the unexposed portions of the photosensitive resin composition layer 12 are removed. As a development method, a conventionally known method can be applied. Specifically, the flexographic printing plate master is exposed as described above, and then the unexposed portions are washed away with a solvent for solvent development or a developer for water development, or the unexposed portions are heated to 40°C to 200°C and brought into contact with a predetermined absorbing layer capable of absorbing the unexposed portions, and the absorbing layer is removed, thereby removing the unexposed portions.
[0271] Thereafter, a post-exposure treatment is performed as necessary to produce a flexographic printing plate. As a post-exposure treatment, a method of irradiating the surface with light having a wavelength of 300 nm or less can be used. If necessary, light having a wavelength longer than 300 nm can also be used in combination.
[0272] In the development step, an aqueous developer or a solvent-based developer can be used, and among these, from the viewpoint of environmental friendliness, it is preferable to use an aqueous developer.
[0273] The solvent-based developer used for solvent development of the unexposed area is not particularly limited, but examples thereof include esters such as heptyl acetate and 3-methoxybutyl acetate; hydrocarbons such as petroleum fractions, toluene and decalin; and mixtures of chlorine-based organic solvents such as tetrachloroethylene with alcohols such as propanol, butanol and pentanol. The unexposed area is washed out by spraying from a nozzle or by brushing with a brush.
[0274] The aqueous developer used for developing the unexposed area with water is a developer mainly composed of water, and may be water itself, an alkaline aqueous solution, or a neutral detergent. There are no particular limitations on such aqueous developer, but it may be water mixed with a nonionic or anionic surfactant, a pH adjuster, a cleaning promoter, or the like.
[0275] Examples of the surfactant include anionic surfactants, amphoteric surfactants, nonionic surfactants, etc. These may be used alone or in combination of two or more.
[0276] Examples of anionic surfactants include, but are not limited to, sulfate ester salts, higher alcohol sulfate ester salts, higher alkyl ether sulfate ester salts, sulfated olefins, alkylbenzene sulfonates, α-olefin sulfonates, phosphate ester salts, and dithiophosphate ester salts.
[0277] The amphoteric surfactant is not particularly limited, but examples thereof include amino acid type amphoteric surfactants and betaine type amphoteric surfactants.
[0278] Examples of nonionic surfactants include, but are not limited to, polyethylene glycol surfactants such as higher alcohol ethylene oxide adducts, alkylphenol ethylene oxide adducts, fatty acid ethylene oxide adducts, polyhydric alcohol fatty acid ester ethylene oxide adducts, higher alkylamine ethylene oxide adducts, fatty acid amide ethylene oxide adducts, and polypropylene glycol ethylene oxide adducts; and polyhydric alcohol surfactants such as glycerol fatty acid esters, pentaerythritol fatty acid esters, sorbitol and sorbitan fatty acid esters, polyhydric alcohol alkyl esters, and fatty acid amides of alkanolamines. The alkaline aqueous solution also contains a pH adjuster.
[0279] The pH adjuster may be either an organic material or an inorganic material, but is preferably one that can adjust the pH to at least 9. The pH adjuster is not particularly limited, but examples thereof include sodium hydroxide, sodium carbonate, potassium carbonate, sodium silicate, sodium metasilicate, and sodium succinate.
[0280] Development can also be performed by heat. In the case of thermal development, no solvent is used, but instead, the photosensitive resin composition layer and the intermediate layer are heated in contact with an absorbent material after imagewise exposure. Absorbent layers for thermal development include nonwoven materials, paper materials, woven fibers, open-cell foams, and porous materials. Among these, preferred absorbent layers are nonwoven materials made of nylon, polyester, polypropylene, polyethylene, and combinations of these nonwoven materials. Particularly preferred absorbent layers are continuous nonwoven webs of nylon or polyester.
[0281] 5. Flexographic printing method The flexographic printing method of the present embodiment includes a printing plate manufacturing step of manufacturing a flexographic printing plate by the above-mentioned flexographic printing plate manufacturing method using the above-mentioned flexographic printing original plate, and a printing step of printing using the flexographic printing plate manufactured in the printing plate manufacturing step.
[0282] The step of printing using a flexographic printing plate is not particularly limited as long as it is a method in which ink is applied to the raised portions of the flexographic printing plate and the ink is transferred to a substrate. EXAMPLES
[0283] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples.
[0284] [Production Example 1] (Synthesis of hydrophilic copolymer) A pressure-resistant reactor equipped with a stirrer and a temperature-controlling jacket was initially charged with 125 parts by mass of water and 2 parts by mass of the ammonium salt of (α-sulfo(1-nonylphenoxy)methyl-2-(2-propenyloxy)ethoxy-poly(oxy-1,2-ethanediyl) "ADEKA REASOAP" (manufactured by ADEKA) as a reactive emulsifier, and the internal temperature was raised to 80°C. 10 parts by mass of styrene, 60 parts by mass of butadiene, 23 parts by mass of butyl acrylate, 5 parts by mass of methacrylic acid, An oily mixed liquid of a monomer mixture consisting of 2 parts by mass of acrylic acid and 2 parts by mass of t-dodecyl mercaptan and an aqueous solution consisting of 28 parts by mass of water, 1.2 parts by mass of sodium peroxodisulfate, 0.2 parts by mass of sodium hydroxide, and 2 parts by mass of the ammonium salt of (α-sulfo(1-nonylphenoxy)methyl-2-(2-propenyloxy)ethoxy-poly(oxy-1,2-ethanediyl) were added at a constant flow rate over 5 hours for the oily mixed liquid and 6 hours for the aqueous solution.
[0285] The temperature of 80°C was then maintained for 1 hour to complete the polymerization reaction, and the copolymer latex was obtained, which was then cooled. The pH of the copolymer latex thus produced was adjusted to 7 with sodium hydroxide, after which unreacted monomers were removed by steam stripping, and the mixture was filtered through a 200-mesh wire net. Finally, the solid content of the filtrate was adjusted to 40% by mass, to obtain an aqueous dispersion of the hydrophilic copolymer. The aqueous dispersion of the hydrophilic copolymer thus obtained was dried up in a vacuum dryer at 50°C to remove water, and the hydrophilic copolymer was obtained.
[0286] [Production Example 2] (Preparation of base film (support)) To prepare a solution for the adhesive layer to be coated on the support (base film), 55 parts by mass of Tufprene 912 (trade name, manufactured by Asahi Kasei Corporation), a block copolymer of styrene and 1,3-butadiene, 38 parts by mass of paraffin oil (average carbon number 33, average molecular weight 470, density at 15°C 0.868), 2.5 parts by mass of 1,9-nonanediol diacrylate, 1.5 parts by mass of 2,2-dimethoxy-phenylacetophenone, 3 parts by mass of Epoxy Ester 3000M (trade name, manufactured by Kyoeisha Chemical Co., Ltd.), and 1.5 parts by mass of Varifast Yellow 3150 (trade name, manufactured by Orient Chemical Industry Co., Ltd.) were dissolved in toluene to obtain a solution with a solids content of 25%.
[0287] Then, using a knife coater, the adhesive was applied to one side of a 100 μm thick polyester film so that the ultraviolet light transmittance (UV transmittance) was 10%, and dried at 80° C. for 1 minute to obtain a support (base film) having an adhesive layer. The UV transmittance of the support was calculated by measuring the transmission intensity with a UV illuminometer MO-2 type (manufactured by Oak Manufacturing Co., Ltd., product name) using an ultraviolet exposure machine AFP-1500 (manufactured by Asahi Kasei Corporation, product name).
[0288] [Production Example 3] (Preparation of film having infrared ablation layer) 65% by mass of Asaflex 810 (trade name, manufactured by Asahi Kasei Corporation), a block copolymer of styrene and 1,3-butadiene, and 35% by mass of carbon black as an infrared-sensitive material were kneaded in a kneader and cut into pellets. 90 parts by mass of the pellets and 10 parts by mass of 1,6-hexanediol adipate were then dissolved using ultrasound in a mixed solvent prepared with a mass ratio of ethyl acetate / butyl acetate / propylene glycol monomethyl ether acetate = 50 / 30 / 20 to prepare a uniform solution with a solid content of 12% by mass.
[0289] Next, this solution is applied to a polyester film with a thickness of 100 μm to become a cover sheet, so that the coating amount after drying is 4 to 5 g / m 2 and dried at 80°C for 1 minute to obtain a film having an ultraviolet shielding layer (infrared ablation layer) that can be ablated by infrared rays. The optical density of this film having an infrared ablation layer was measured with DM-500 (trade name, manufactured by Dainippon Screen Mfg. Co., Ltd.) and found to be 3 to 4.
[0290] [Production Example 4] (Preparation of cover film (film having intermediate layer and infrared ablation layer)) A solution was prepared with a mass ratio of ethanol / distilled water = 10 / 90, and 90 mass% of a polyester emulsion compound Pluscoat Z730 (manufactured by GOO Chemical Co., Ltd., Tg 46°C, number average molecular weight 3,000, acid value 40 mgKOH / g), 5 mass% of a polyurethane emulsion compound WLS-202 (manufactured by DIC Corporation, Tg -50°C), and 5 mass% of a polyether modified silicone oil KF-351A (manufactured by Shin-Etsu Chemical Co., Ltd.) were added and stirred to prepare an intermediate layer coating liquid.
[0291] Next, the intermediate layer coating liquid was applied to the infrared ablation layer-forming surface side of the film having the infrared ablation layer produced in the above Production Example 3 using a bar coater so that the film thickness after drying would be 3 μm. Then, it was dried at 100° C. for 4 minutes to obtain a cover film having an intermediate layer and an infrared ablation layer.
[0292] Example 1 (Preparation of flexographic printing plates) 32 parts by mass of the hydrophilic copolymer obtained in the above Production Example 1 and 28 parts by mass of a styrene-butadiene-styrene copolymer [D-KX405: manufactured by Kraton] were mixed at 140°C using a pressure kneader, and then a liquid mixture of 32 parts by mass of liquid polybutadiene [LBR-352: manufactured by Kuraray Co., Ltd.], 8 parts by mass of 1,6-hexanediol dimethacrylate, 2 parts by mass of 2,2-dimethoxyphenylacetophenone, 1 part by mass of 2,6-di-t-butyl-p-cresol, and 1 part by mass of carbinol-modified silicone oil [KF-6000: manufactured by Shin-Etsu Chemical Co., Ltd.] was gradually added over 15 minutes, and the mixture was kneaded for an additional 20 minutes after the addition was completed, to obtain a photosensitive resin composition 1.
[0293] Next, the photosensitive resin composition 1 was placed in an extrusion molding machine and extruded through a T-shaped die. The side of the base film (support) obtained in the above Production Example 2 on which the adhesive layer was formed was bonded to one side of the photosensitive resin composition 1, and a release film (Diafoil MRV100, manufactured by Mitsubishi Chemical Corporation) was bonded to the side of the photosensitive resin composition layer opposite the support laminate side, thereby obtaining a laminate of the support and the photosensitive resin composition layer.
[0294] Next, the release film was peeled off, and the cover film having the intermediate layer and the infrared ablation layer obtained in Production Example 4 above was laminated so that the intermediate layer was in contact with the photosensitive resin composition layer to obtain a flexographic printing original plate.
[0295] (Flexographic printing plate manufacturing) The support side (PET coated with adhesive) of the flexographic printing plate was exposed using an ultraviolet exposure machine "JE-A2-SS" (product name, manufactured by Nippon Denshi Seiki Co., Ltd.) so that the pattern height (RD) after curing was approximately 0.5 mm.
[0296] Next, the cover sheet of the infrared ablation layer was peeled off, and a halftone image (AM 150 lines, data 25% halftone) was drawn on the infrared ablation layer using a CDI Spark4260 (product name, manufactured by ESKO GRAPHIC), and then the infrared ablation layer side was exposed to 8000 mJ under atmospheric conditions using an exposure machine.
[0297] After exposure, an aqueous solution (aqueous developer) of 1% polyoxyalkylene alkyl ether (Newcol 2308: Nippon Nyukazai) and 1% potassium carbonate was prepared, and the plate was washed (developed) at 40°C using a JEOL cleaning machine (JOW-A3-P) to remove the unexposed areas. After drying at 50°C for 10 minutes, the plate was post-exposed with an ultraviolet sterilization lamp and an ultraviolet chemical lamp to remove surface tackiness, and a flexographic printing plate was obtained.
[0298] Example 2 In manufacturing a flexographic printing plate base, when preparing the intermediate layer coating liquid described in Manufacturing Example 4 above, 75 mass% of Pluscoat Z-730, a polyester emulsion, 15 mass% of WLS-202, a polyurethane emulsion compound, and 10 mass% of KF-351A, a polyether modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare the intermediate layer coating liquid. Next, the intermediate layer was applied so that the film thickness after drying would be 15 μm. The other conditions were the same as in Example 1, and a flexographic printing original plate and a flexographic printing plate were obtained.
[0299] Example 3 In the manufacture of the flexographic printing plate, when preparing the intermediate layer coating liquid described in the above-mentioned manufacturing example 4, 75% by mass of PLASCOAT Z-730, which is a polyester emulsion, 15% by mass of A-7090 (manufactured by Asahi Kasei Corporation, Tg 6°C), which is a styrene-butadiene copolymer latex, and 10% by mass of KF-351A, which is a polyether modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. Next, when applying the intermediate layer, it was applied so that the film thickness after drying would be 30 μm. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0300] Example 4 In the manufacture of a flexographic printing plate, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 60% by mass of Vylonal MD-2000 (manufactured by Toyobo Co., Ltd., Tg 67°C, number average molecular weight 18,000, acid value <2mgKOH / g), a polyester emulsion compound, 35% by mass of WLS-202, a polyurethane emulsion compound, and 5% by mass of KF-351A, a polyether modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. Next, when applying the intermediate layer, it was applied so that the film thickness after drying would be 10 μm. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0301] Example 5 In the manufacture of a flexographic printing plate, 60% by mass of a polyester emulsion compound PLASCOAT Z-221 (manufactured by GOO Chemical Co., Ltd., Tg 47°C, number average molecular weight 14,000, acid value <5mgKOH / g), 30% by mass of a polyurethane emulsion compound WLS-202, and 10% by mass of a polyether modified silicone oil KF-351A were added and stirred to prepare an intermediate layer coating liquid. Next, when applying the intermediate layer, it was applied so that the film thickness after drying would be 2.5μm. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0302] Example 6 In the manufacture of a flexographic printing plate, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 50% by mass of PLASCOAT Z-687 (manufactured by GOOKAGAKU Co., Ltd., Tg 110°C, number average molecular weight 26,000, acid value <5mgKOH / g) which is a polyester emulsion compound, 40% by mass of WLS-202 which is a polyurethane emulsion compound, and 10% by mass of KF-351A which is a polyether modified silicone oil were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. Next, when applying the intermediate layer, it was applied so that the film thickness after drying would be 2.1 μm. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained. Other conditions were the same as in Example 1, and a flexographic printing original plate and a flexographic printing plate were obtained.
[0303] Example 7 In the manufacture of a flexographic printing plate, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 79% by mass of Pluscoat Z-730, a polyester emulsion, 10% by mass of WLS-202, a polyurethane emulsion compound, 1% by mass of Somasif MEB-3 (manufactured by Katakura Co-op Agri Co., Ltd.), a water-swellable synthetic mica, and 10% by mass of KF-351A, a polyether-modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0304] Example 8 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 60% by mass of PLASCOAT Z-730, which is a polyester emulsion, 26% by mass of WLS-202, which is a polyurethane emulsion compound, 4% by mass of Somasif MEB-3, which is a water-swellable synthetic mica, and 10% by mass of KF-351A, which is a polyether-modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0305] Example 9 In the manufacture of a flexographic printing plate, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 60% by mass of PLASCOAT Z-221, which is a polyester emulsion compound, 26% by mass of WLS-202, which is a polyurethane emulsion compound, 4% by mass of Aluminasol 10N (manufactured by Kawaken Fine Chemicals Co., Ltd.), which is a water-dispersed aluminum hydroxide, and 10% by mass of KF-351A, which is a polyether-modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0306] Example 10 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 80 mass% of Vylonal MD-2000, 15 mass% of L-7430 (manufactured by Asahi Kasei Corporation, Tg-5°C), which is a styrene-butadiene copolymer latex (emulsion compound (B)), and 5 mass% of KF-351A were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0307] Example 11 In the manufacture of a flexographic printing plate, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 40% by mass of PLASCOAT Z-730, which is a polyester emulsion, 42% by mass of WLS-202, which is a polyurethane emulsion compound, 8% by mass of Somasif ME300B4T (manufactured by Katakura Co-op Agri Co., Ltd.), which is a water-swellable synthetic mica, and 10% by mass of KF-351A, which is a polyether-modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0308] Example 12 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 70 mass% of Vylonal MD-2000, 20 mass% of L-7430, 5 mass% of Aluminasol 10N (manufactured by Kawaken Fine Chemicals Co., Ltd.), which is water-dispersed aluminum hydroxide, and 5 mass% of KF-351A were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0309] Example 13 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above Manufacturing Example 4, 70 mass% of Vylonal MD-2000, 20 mass% of L-7430, 5 mass% of Carbodilite V-02 (manufactured by Nisshinbo Chemical Co., Ltd.), which is a carbodiimide crosslinking agent, and 5 mass% of KF-351A were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0310] Example 14 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 70 mass% of Vylonal MD-2000, 20 mass% of L-7430, 5 mass% of SU-268A (manufactured by Meisei Chemical Industry Co., Ltd.), which is an isocyanate-based crosslinking agent, and 5 mass% of KF-351A were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0311] Example 15 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 40% by mass of PLASCOAT Z-730, a polyester emulsion, 38% by mass of WLS-202, a polyurethane emulsion compound, 12% by mass of Somasif MEB-3, a water-swellable synthetic mica, and 10% by mass of KF-351A, a polyether-modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0312] Example 16 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 40% by mass of PLASCOAT Z-730, a polyester emulsion, 38% by mass of WLS-202, a polyurethane emulsion compound, 12% by mass of Somasif MEB-3, a water-swellable synthetic mica, and 10% by mass of KF-351A, a polyether-modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0313] Example 17 In the manufacture of a flexographic printing plate, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 70% by mass of PLASCOAT Z-730, which is a polyester emulsion, 15% by mass of WLS-202, which is a polyurethane emulsion compound, 5% by mass of SU-268A (manufactured by Meisei Chemical Industry Co., Ltd.), which is an isocyanate-based crosslinking agent, and 10% by mass of KF-351A, which is a polyether-modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0314] Example 18 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 40% by mass of PLASCOAT Z-730, which is a polyester emulsion, 37% by mass of WLS-202, which is a polyurethane emulsion compound, 8% by mass of Somasif MEB-3, which is a water-swellable synthetic mica, 5% by mass of Carbodilite V-02 (manufactured by Nisshinbo Chemical Co., Ltd.), which is a carbodiimide-based crosslinking agent, and 10% by mass of KF-351A, which is a polyether-modified silicone oil, were added and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0315] Example 19 [Production Example 5] (Synthesis of polyester emulsion) A mixed liquid was prepared by adding 0.01 parts by mass of titanium tetrabutoxide as a catalyst to a 1000 ml reaction vessel equipped with a stirrer, a nitrogen gas inlet, a thermometer, a rectification column, and a cooler, and adding 146 parts by mass of dimethyl terephthalate, 20 parts by mass of dodecanedioic acid, and 32 parts by mass of trimellitic anhydride as polycarboxylic acid components, and adding 62 parts by mass of ethylene glycol and 104 parts by mass of 2,2-dimethyl-1,3-propanediol as polyol components. This mixed liquid was heated to 200°C under normal pressure and in a nitrogen atmosphere while stirring and mixing, and then gradually heated to 250°C over 4 hours to allow the transesterification reaction to proceed.
[0316] Next, while stirring this mixed solution in a reaction vessel, the pressure was gradually reduced from normal pressure to 0.67 hPa (0.5 mmHg) at a temperature of 250°C, and the mixture was stirred for 2 hours in this state to allow the polycondensation reaction to proceed. As a result, a polyester resin A was obtained.
[0317] 100 parts by mass of the obtained polyester resin A, 40 parts by mass of butyl cellosolve, 255 parts by mass of water, and 5 parts by mass of 25% aqueous ammonia were mixed and heated and stirred at a temperature of 80 to 90°C for 2 hours while stirring, thereby obtaining polyester emulsion A in which polyester resin was dispersed at a concentration of 25% by mass. The obtained polyester emulsion A had a glass transition temperature Tg of 40°C, a number average molecular weight of 3,000, and an acid value of 55 mgKOH / g.
[0318] In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 60 mass% of the polyester emulsion A synthesized in Manufacturing Example 5, 26 mass% of the polyurethane emulsion compound WLS-202, 4 mass% of the water-swellable synthetic mica Somasif MEB-3, and 10 mass% of the polyether-modified silicone oil KF-351A were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0319] Example 20 In the synthesis of the polyester emulsion described in the above Production Example 5, 0.01 parts by mass of titanium tetrabutoxide as a catalyst was added to a 1000 ml reaction vessel equipped with a stirrer, a nitrogen gas inlet, a thermometer, a rectifying column, and a cooler, and 107 parts by mass of dimethyl terephthalate, 30 parts by mass of dodecanedioic acid, and 63 parts by mass of trimellitic anhydride were added as polyvalent carboxylic acid components, and 62 parts by mass of ethylene glycol and 104 parts by mass of 2,2-dimethyl-1,3-propanediol were added as polyol components to prepare a mixed liquid. The other conditions were the same as those of Production Example 5, and polyester resin B was obtained.
[0320] 100 parts by mass of this polyester resin B, 40 parts by mass of butyl cellosolve, 254 parts by mass of water, 5 parts by mass of 25% ammonia water, and 1 part by mass of sodium hydroxide were mixed and held at a temperature of 80 to 90°C for 2 hours while stirring to obtain polyester emulsion B. The obtained polyester emulsion B had a glass transition temperature Tg of 43°C, a number average molecular weight of 3,000, and an acid value of 97 mgKOH / g.
[0321] Next, in the manufacture of a flexographic printing plate, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 60% by mass of polyester emulsion B, 26% by mass of WLS-202, a polyurethane emulsion compound, 4% by mass of Somasif MEB-3, a water-swellable synthetic mica, and 10% by mass of KF-351A, a polyether-modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0322] Example 21 In the synthesis of the polyester emulsion described in the above Production Example 5, 0.01 parts by mass of titanium tetrabutoxide as a catalyst was added to a 1000 ml reaction vessel equipped with a stirrer, a nitrogen gas inlet, a thermometer, a rectifying column, and a cooler, and 161 parts by mass of dimethyl terephthalate, 20 parts by mass of dodecanedioic acid, and 15 parts by mass of trimellitic anhydride were added as polycarboxylic acid components, and 62 parts by mass of ethylene glycol and 104 parts by mass of 2,2-dimethyl-1,3-propanediol were added as polyol components to prepare a mixed liquid. The other conditions were the same as in Production Example 5 to obtain polyester emulsion C. The obtained polyester emulsion C had a glass transition temperature Tg of 39° C., a number average molecular weight of 3,000, and an acid value of 26 mgKOH / g.
[0323] Next, in the manufacture of the flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 60% by mass of polyester emulsion C, 26% by mass of WLS-202, a polyurethane emulsion compound, 4% by mass of Somasif MEB-3, a water-swellable synthetic mica, and 10% by mass of KF-351A, a polyether-modified silicone oil, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare the intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0324] Example 22 In the manufacture of the flexographic printing plate, 60% by mass of PLASCOAT Z730, a polyester emulsion compound, 26% by mass of A-7090, a styrene-butadiene copolymer latex, 4% by mass of Somasif MEB-3, a water-swellable synthetic mica, and 10% by mass of KF-351A, a polyether-modified silicone oil, were added and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0325] Example 23 In the manufacture of the flexographic printing plate, 60% by mass of PLASCOAT Z730, a polyester emulsion compound, 26% by mass of SX-1503A (manufactured by Zeon Corporation, Tg-26°C), an acrylonitrile-butadiene copolymer latex, 4% by mass of Somasif MEB-3, a water-swellable synthetic mica, and 10% by mass of KF-351A, a polyether-modified silicone oil, were added and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0326] Example 24 In the manufacture of a flexographic printing plate, 60% by mass of PLASCOAT Z730, a polyester emulsion compound, 26% by mass of LX-111NF (manufactured by Zeon Corporation, Tg-82°C), a butadiene-based latex, 4% by mass of Somasif MEB-3, a water-swellable synthetic mica, and 10% by mass of KF-351A, a polyether-modified silicone oil, were added and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate was obtained.
[0327] Next, in the manufacturing process of the flexographic printing plate, the cover sheet of the infrared ablation layer was peeled off, and a halftone image (AM 150 lines, data 25% halftone) was drawn on the infrared ablation layer in pixel+ mode using a CDI Crystal 4835 (product name, manufactured by ESKO GRAPHIC).
[0328] After drawing, the pattern was exposed simultaneously on both sides, the infrared ablation side and the support side, using an XPS Crystal 4835 (product name, manufactured by ESKO GRAPHIC) with a main UV power density of 311 mW / cm2, a back UV power density of 27 mW / cm2, four passes, and a pixel time of 20 seconds.
[0329] After the exposure, a 1% polyoxyalkylene alkyl ether (Newcol 2308: Nippon Nyukazai) was prepared, and the plate was washed (developed) at 40°C using a Nippon Denshi Seiki washer (JOW-A3-P) to remove the unexposed areas. After drying at 50°C for 10 minutes, the plate was post-exposed with an ultraviolet sterilization lamp and an ultraviolet chemical lamp to remove the tackiness of the surface, to obtain a flexographic printing plate.
[0330] Example 25 In the manufacture of the flexographic printing plate precursor, 80% by mass of PLASCOAT Z730, a polyester emulsion compound, 15% by mass of AQ nylon T-70 (manufactured by Toray Industries, Inc.), a water-soluble polyamide, and 5% by mass of KF-351A, a polyether-modified silicone oil, were added and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0331] Example 26 In the production of the photosensitive resin composition, 60 parts by mass of styrene-butadiene-styrene copolymer [D-KX405: manufactured by Kraton] was mixed at 180°C using a pressure kneader, and then a liquid mixture of 32 parts by mass of liquid polybutadiene [LBR-352: manufactured by Kuraray Co., Ltd.], 8 parts by mass of 1,9-nonanediol diacrylate, 5 parts by mass of 1,6-hexanediol dimethacrylate, 2 parts by mass of 2,2-dimethoxyphenylacetophenone, 1 part by mass of 2,6-di-t-butyl-p-cresol, and 1 part by mass of amino-modified silicone oil [KF-8000: manufactured by Shin-Etsu Chemical Co., Ltd.] was gradually added over 15 minutes, and after the addition was completed, the mixture was kneaded for another 20 minutes to obtain a photosensitive resin composition 2. The other conditions were the same as in Example 8, and a flexographic printing plate precursor was obtained.
[0332] Next, the support side (PET coated with adhesive) of the flexographic printing plate was exposed using an ultraviolet exposure machine "JE-A2-SS" (product name, manufactured by Nippon Denshi Seiki Co., Ltd.) so that the pattern height (RD) after curing was approximately 0.5 mm.
[0333] Next, the cover sheet of the infrared ablation layer was peeled off, and a halftone image (AM 150 lines, data 25% halftone) was drawn on the infrared ablation layer using a CDI Spark4260 (product name, manufactured by ESKO GRAPHIC), and then the infrared ablation layer side was exposed to 8000 mJ under atmospheric conditions using an exposure machine.
[0334] After the exposure, the plate was fixed to the rotating drum of an "AFP-1500" developing machine (trade name, manufactured by Asahi Kasei Corporation) using 3-methoxybutyl acetate as a developer by attaching double-sided tape to the side that had been subjected to the above-mentioned back exposure, and developed at a liquid temperature of 25° C. for 5 minutes and dried at 60° C. for 2 hours. To remove surface tackiness, the plate was post-exposed with an ultraviolet sterilization lamp and an ultraviolet chemical lamp to obtain a flexographic printing plate.
[0335] Example 27 A flexographic printing plate precursor was obtained in the same manner as in Example 19. Next, the support (PET coated with adhesive) side of the flexographic printing plate precursor was exposed to light using an ultraviolet exposure machine "JE-A2-SS" (trade name, manufactured by Nippon Denshi Seiki Co., Ltd.) so that the pattern height (RD) after curing was about 0.5 mm.
[0336] Next, the cover sheet of the infrared ablation layer was peeled off, and a halftone image (AM 150 lines, data 25% halftone) was drawn on the infrared ablation layer using a CDI Spark4260 (product name, manufactured by ESKO GRAPHIC), and then the infrared ablation layer side was exposed to 8000 mJ under atmospheric conditions using an exposure machine.
[0337] After exposure, the flexographic printing master was heated to 170° C. in a CYREL® FAST TD1000 thermal processor and the unexposed areas were removed by contacting with a development medium, which was a polyester nonwoven. To remove surface tackiness, the plate was post-exposed to an ultraviolet sterilization lamp and an ultraviolet chemical lamp to obtain a flexographic printing plate.
[0338] Comparative Example 1 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above Manufacturing Example 4, 50% by mass of Vylonal MD-1400 (manufactured by Toyobo Co., Ltd., Tg 20°C), which is a polyester emulsion compound, and 50% by mass of Gohsenol KL-03 (manufactured by Nippon Synthetic Chemical Industry Co., Ltd.), which is a polyvinyl alcohol, were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare the intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0339] Comparative Example 2 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 50% by mass of XL-006 (manufactured by Asahi Kasei Corporation, Tg-6°C), which is a styrene-butadiene copolymer latex (emulsion compound), 40% by mass of WLS-202, and 10% by mass of KF-351A were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0340] Comparative Example 3 In the manufacture of a flexographic printing plate, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 20% by mass of SX1503 (manufactured by Zeon Corporation, Tg-26°C) which is an acrylonitrile butadiene copolymer latex (emulsion compound) was added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, 50% by mass of PVA405 (manufactured by Kuraray Co., Ltd.) which is a polyvinyl alcohol, and 30% by mass of Sunflex SE270 (manufactured by Sanyo Chemical Industries, Ltd.) which is an aliphatic polyhydric alcohol-based polyether polyol, and the intermediate layer coating liquid was prepared by adding and stirring. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0341] Comparative Example 4 In the manufacture of a flexographic printing plate precursor, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 10% by mass of L-7430, 75% by mass of AQ nylon T-70, 5% by mass of water-swellable synthetic mica Somasif MEB-3 (manufactured by Katakura Co-op Agri Co., Ltd.), and 10% by mass of KF-351A were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0342] Comparative Example 5 In the production of the flexographic printing plate precursor, when applying the intermediate layer described in the above Production Example 4, 100% by mass of PLASCOAT Z-221, a polyester emulsion compound, was added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90 and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0343] Comparative Example 6 In the manufacture of the flexographic printing plate, when preparing the intermediate layer coating liquid described in the above-mentioned Manufacturing Example 4, 20% by mass of Vylon 200 (manufactured by Toyobo Co., Ltd.), which is a copolymer polyester resin, and 80% by mass of Vylon 300 (manufactured by Toyobo Co., Ltd.), which is a copolymer polyester resin, were added to a solution prepared with a mass ratio of toluene / methyl ethyl ketone = 50 / 50, and stirred to prepare the intermediate layer coating liquid. Next, the intermediate layer coating liquid was applied so that the film thickness after drying would be 0.7 μm. The other conditions were the same as in Example 1, and a flexographic printing plate and a flexographic printing plate were obtained.
[0344] Comparative Example 7 In the production of a flexographic printing plate precursor, when applying the intermediate layer described in Production Example 4 above, 67% by mass of a polyester emulsion compound PLASCOAT Z-446 (manufactured by GOO Chemical Co., Ltd., Tg 47°C, number average molecular weight 16,000, acid value <5 mgKOH / g) and 33% by mass of polyvinylpyrrolidone solution K60 (manufactured by Sigma-Aldrich) were added to a solution prepared with a mass ratio of ethanol / distilled water = 10 / 90, and stirred to prepare an intermediate layer coating liquid. The other conditions were the same as in Example 1, and a flexographic printing plate precursor and a flexographic printing plate were obtained.
[0345] [Measurement of physical properties] <Method of measuring tensile stress-strain curve> 1. Sample Preparation The support side (PET coated with adhesive) of the flexographic printing plate precursor was exposed to 8,000 mJ using an ultraviolet exposure machine "JE-A2-SS" (trade name, manufactured by Nippon Denshi Seiki Co., Ltd.). Next, the cover sheet of the infrared ablation layer was peeled off, and the entire surface of the infrared ablation layer was removed using a CDI Spark4260 (manufactured by ESKO GRAPHIC, trade name) to expose the intermediate layer.
[0346] Then, the composition was immersed in distilled water, a mixture of distilled water and ethanol, or an organic solvent in which the composition was soluble, and ultrasonic extraction was performed for 30 minutes. The extract was dried to obtain a dried intermediate layer composition.
[0347] The obtained dried intermediate layer composition was sandwiched between two release-treated PET films each having a thickness of 100 μm, and molded into a thickness of 100 μm in a press machine heated to 150° C. The obtained molded product was punched out using a tensile No. 8 dumbbell punching blade (manufactured by Kobunshi Keiki Co., Ltd.) with a thickness of 100 μm in accordance with JIS K 6251 (2017) to obtain a test specimen.
[0348] The tensile stress-strain curves of Examples 2 and 6 and Comparative Example 1 obtained as described above are collectively shown in FIG. 4, and the tensile stress-strain curves of Examples 2 and 6 and Comparative Example 1 are respectively shown in FIGS.
[0349] 2. Equipment, measurement conditions, etc. The test pieces were subjected to tensile fracture tests using a bench-top precision universal testing machine (Shimadzu Corporation, Autograph AGS-X) at a crosshead speed of 200 mm / min and a chuck distance of 30 mm. Data was recorded using the accompanying software (TRAPEZIUM LITE X). Measurements were performed at n=5 points, and the average value was used. A representative measurement example is shown in Figure x.
[0350] <Measurement of water contact angle> 1. Sample Preparation The support side (PET coated with adhesive) of the flexographic printing plate precursor was exposed to 8,000 mJ using an ultraviolet exposure machine "JE-A2-SS" (trade name, manufactured by Nippon Denshi Seiki Co., Ltd.). Next, the cover sheet of the infrared ablation layer was peeled off, and the entire surface of the infrared ablation layer was removed using a CDI Spark4260 (manufactured by ESKO GRAPHIC, trade name) to expose the intermediate layer.
[0351] 2. Equipment, measurement conditions, etc. Using a contact angle meter AD-31 (Kyowa Interface Science Co., Ltd.), 0.2 mL of distilled water was dropped onto the exposed intermediate layer, and after leaving it to stand for 3 minutes, the contact angle was measured at n = 5 points or more, and the average value was used.
[0352] <Method for measuring Tg of emulsion compounds> The glass transition temperature Tg of an emulsion compound is a value measured by DSC in accordance with JIS K 7121 (1987). Specifically, an emulsion compound is placed in a differential scanning calorimeter, heated to (Tg+50°C) at a heating rate of 10°C / min, held for 10 minutes, and then rapidly cooled. The glass transition temperature (Tg) is read from the obtained differential thermal curve.
[0353] In addition, commercially available products can be used as the emulsion compound. When the emulsion compound is a commercially available product, the Tg is preferentially adopted from the catalog data of the commercially available product. In addition, although the unit is not described in the following Tables 1 to 3 for convenience, the unit of Tg is Celsius (°C).
[0354] <Method of measuring number average molecular weight (Mn) by gel permeation column chromatography (GPC)> 1. Sample preparation 0.1 g of emulsion compound, which is adjusted to a solid content of 20% by mass by adding water as necessary, is added with about 1 g of cation exchange resin, which is washed and rinsed according to a conventional method, to remove cations. Next, 50 ml of tetrahydrofuran is added and left for 2 hours to dissolve. Then, the mixture is filtered through a polytetrafluoroethylene membrane filter (pore size 3 μm, manufactured by ADVANTEC), and the filtrate is used as a measurement sample.
[0355] 2. Equipment, measurement conditions, etc. GPC measurement of the emulsion compound was carried out using the following apparatus and measurement conditions. When the obtained GPC chart shows two peaks, the one with the larger number average molecular weight is used in this embodiment. Equipment: Tosoh HLC-8220 GPC Columns: The following four columns were connected in series for separation. Tosoh TSKgel GMH XL Tosoh TSKgel GMH XL Tosoh TSKgel GMH XLL Tosoh TSKgel GMH XLL Column temperature: 40℃ Solvent: Tetrahydrofuran Flow rate: 1mL / min Detector: RI Calibration curve: Standard polystyrene
[0356] [Characteristics evaluation] <Evaluation of developability> The flexographic printing original plates obtained in Examples 1 to 27 and Comparative Examples 1 to 7 were developed at 40° C. using a cleaning machine (JOW-A3-P) manufactured by Nippon Denshi Seiki Co., Ltd., with an aqueous solution of 1% polyoxyalkylene alkyl ether (Newcol 2308: manufactured by Nippon Nyukazai Co., Ltd.) and 1% potassium carbonate as a developer. The removal status of the infrared ablation layer and intermediate layer was confirmed after 20 seconds, 40 seconds, 60 seconds, and 180 seconds of development.
[0357] In addition, the flexographic printing plate obtained in Example 19 was developed by the method described in Example 19, and the removal status of the infrared ablation layer and intermediate layer was confirmed after 20 seconds, 40 seconds, 60 seconds, and 180 seconds of development.
[0358] In addition, the flexographic printing plate precursor obtained in Example 20 was developed by the method described in Example 20, and the removal status of the infrared ablation layer and intermediate layer was confirmed after 20 seconds, 40 seconds, 60 seconds, and 180 seconds of development.
[0359] Based on the cleaning time required to uniformly remove the infrared ablation layer and the intermediate layer, the developability was evaluated according to the following evaluation criteria. If the evaluation criteria below give a score of 3 or more, the composition can be used without any problems in practice. (Evaluation Criteria) 5: The cleaning time required for removal is 20 seconds or less. 4: The cleaning time required for removal is more than 20 seconds and less than 40 seconds. 3: The cleaning time required for removal is more than 40 seconds and less than 60 seconds. 2: The cleaning time required for removal is more than 60 seconds and less than 180 seconds. 1: The cleaning time required for removal exceeded 180 seconds or removal was not uniform.
[0360] <Plate reproducibility: Evaluation of the variation in size of halftone dot images> Two samples of each of the flexographic printing original plates obtained in the Examples and Comparative Examples were prepared, and one sample was stored for 7 days in a thermo-hygrostat PH-3K (manufactured by ESPEC) set at a temperature of 30° C. and a relative humidity of 10% RH, while the other sample was stored for 1 month in a thermo-hygrostat PH-3K set at a temperature of 30° C. and a relative humidity of 90% RH. Thereafter, a flexographic printing plate was obtained by the same method as in the manufacturing method of the flexographic printing plate described in Example 1.
[0361] The top area ratio of the halftone dot image on the obtained flexographic printing plate (AM150 lines, 25% halftone dot area) was measured at different measurement points, n=20 points each, using FLEX3PRO (Avid Flex). Then, based on the difference in the average value of the top area ratio of the halftone dots for two samples stored in different environments, the plate reproducibility was evaluated according to the following evaluation criteria. Note that if the following evaluation criteria score is 3 or higher, the plate can be used without any problems in practical use. (Evaluation Criteria) 5: The difference in area ratio of the top of the halftone dots is 0.2% or less. 4: The difference in the area ratio of the top of the halftone dots exceeds 0.2% and is 0.3% or less. 3: The difference in the area ratio of the top of the halftone dots exceeds 0.3% and is 0.6% or less. 2: The difference in the area ratio of the top of the halftone dots is more than 0.6% and is 1.0% or less. 1: The difference in the area ratio of the top of the halftone dots is more than 1.0% and is 2.0% or less. 0: The difference in area ratio of the top of the halftone dots exceeds 2.0%.
[0362] <Evaluation of reattachment of ablation layer residue to plate surface> The flexographic printing original plates obtained in the Examples and Comparative Examples were stored for one month in a thermo-hygrostat PH-3K set at a temperature of 30°C and a relative humidity of 90% RH, and then the flexographic printing plates were produced using the flexographic printing original plates in a manner similar to the flexographic printing plate producing method described in Example 1.
[0363] The halftone image area of the obtained flexographic printing plate was observed with a microscope (Keyence, VHX-1000) at a magnification of 50x and a field of view of 20cm x 20cm, and the number of adhering debris from the infrared ablation layer was counted. Based on the number of debris counted, the re-adhesion of the debris from the ablation layer to the plate surface was evaluated according to the following evaluation criteria. Note that if the following evaluation criteria score is 3 or higher, the plate can be used without any problems in practice. (Evaluation Criteria) 5: There is no residue from the infrared ablation layer. 4: The number of attached infrared ablation layer particles is 2 or less. 3: The number of attached infrared ablation layer particles is between 3 and 5. 2: The number of attached infrared ablation layer particles is between 6 and 10. 1: The number of attached infrared ablation layer particles is 11 or more.
[0364] <Pinhole (PH) evaluation> The flexographic printing original plates obtained in the above [Example] and [Comparative Example] were cut into five pieces measuring 20 cm x 20 cm to prepare samples. After removing the cover film from the infrared ablation layer, these samples were wrapped around the drum of a laser drawing machine (CDI Sperk 2530) and left to stand for 10 minutes, and then observed with a microscope (Keyence, VHX-1000) at a magnification of 50x and a field of view of 20cm x 20cm, and the number of pinholes with a major axis of 20μm or more in the infrared ablation layer was counted, the average value was taken, the value (pieces / m2) was calculated, and the sample was evaluated according to the following 1 to 5. In the following evaluations, the higher the number, the more preferable it is, and a number of 3 or more means that the sample can be used without any problems in practice. 5: The average number of pinholes is less than 2 (pieces / m2). 4: The average number of pinholes is 2 or more (pieces / m2) and less than 5 (pieces / m2). 3: The average number of pinholes is 5 or more (pieces / m2) and less than 10 (pieces / m2). 2: The average number of pinholes is 10 or more (pieces / m2) and less than 20 (pieces / m2). 1: The average number of pinholes is 20 or more (pcs / m2).
[0365] The above results are shown in Tables 1 to 3 below.
[0366] [Table 1]
[0367] [Table 2]
[0368] [Table 3]
[0369] (component) The components used in the table are as follows: <Emulsion compounds (A) and (B)> Vylonal MD-2000: Polyester emulsion, manufactured by Toyobo Co., Ltd. Vylonal MD-1400: Polyester emulsion, manufactured by Toyobo Co., Ltd. Pluscoat Z221: Polyester emulsion, manufactured by GOO Chemical Co., Ltd. Pluscoat Z446: Polyester emulsion, manufactured by GOO Chemical Co., Ltd. Pluscoat Z730: Polyester emulsion, manufactured by GOO Chemical Co., Ltd. Pluscoat Z687: Polyester emulsion, manufactured by GOO Chemical Co., Ltd. A-7090: Styrene-butadiene copolymer latex, manufactured by Asahi Kasei Corporation L-7430: Styrene-butadiene copolymer latex, manufactured by Asahi Kasei Corporation XL-006: Styrene-butadiene copolymer latex, manufactured by Asahi Kasei Corporation Hydran WLS-202: Polyurethane emulsion, manufactured by DIC SX1503A: Acrylonitrile-butadiene copolymer latex, manufactured by Zeon Corporation LX-111NF: Polybutadiene latex, manufactured by Zeon Corporation <Inorganic layered compound (C)> Somasif MEB-3: Mica, manufactured by Katakura Coop Agri Somasif ME300B4T: Mica, manufactured by Katakura Coop Agri Co., Ltd. Aluminium Sol 10N: Aluminum oxide, manufactured by Kawaken Fine Chemicals Co., Ltd. <Crosslinking agent (D)> Carbodilite V-02: Carbodiimide crosslinking agent, manufactured by Nisshinbo Chemical Co., Ltd. SU268-A: Isocyanate-based crosslinking agent, manufactured by Meisei Chemical Industry Co., Ltd. <Binder polymer (E)> AQ Nylon T-70: Polyamide, manufactured by Toray Industries, Inc. Gohsenol KL-03: Polyvinyl alcohol, manufactured by Nippon Synthetic Chemical Industry Co., Ltd. PVA405: Polyvinyl alcohol, manufactured by Kuraray Vylon 200: Copolymer polyester resin, manufactured by Toyobo Co., Ltd. Vylon 300: Copolymer polyester resin, manufactured by Toyobo Co., Ltd. Sunflex SE270: Polyalkylene glycol, manufactured by Sanyo Chemical Industries, Ltd. PVP: Polyvinylpyrrolidone solution K60, manufactured by Sigma-Aldrich <Silicone Compounds (F)> KF-351A: Polyether modified silicone oil, manufactured by Shin-Etsu Chemical Co., Ltd. [Industrial Applicability]
[0370] The present invention has industrial applicability as a flexographic printing plate precursor for obtaining a flexographic printing plate.
Claims
1. A support; A photosensitive resin composition layer on the support; The middle class, an infrared ablation layer, in that order; The intermediate layer was molded into a No. 8 dumbbell shape having a thickness of 100 μm in accordance with JIS K 6251 (2017) and measured in a tensile stress-strain curve diagram. The elongation to the breaking point is 5% or more and 200% or less, The elongation at the point where the stress is maximum is 3% or more and 200% or less, The maximum value of the stress is 1.0 MPa or more and 15 MPa or less, The intermediate layer contains a polyester emulsion compound (A) having a glass transition temperature (Tg) of 30° C. or higher, and an emulsion compound (B) or a binder polymer (E) having a glass transition temperature (Tg) of 10° C. or lower. Flexographic printing plate.
2. the intermediate layer has a water contact angle of 60° or more and 90° or less at the interface with the infrared ablation layer 3 minutes after droplet landing; The flexographic printing plate precursor according to claim 1.
3. the intermediate layer has a water contact angle of 70° or more at the interface with the infrared ablation layer 3 minutes after droplet landing; The flexographic printing plate precursor according to claim 1 or 2.
4. The intermediate layer contains the emulsion compound (A) in an amount of 10% by mass or more and 95% by mass or less based on the total amount of the intermediate layer. The flexographic printing plate precursor according to any one of claims 1 to 3.
5. The acid value of the emulsion compound (A) is 20 mgKOH / g or more and 100 mgKOH / g or less. The flexographic printing plate precursor according to any one of claims 1 to 4.
6. The number average molecular weight of the emulsion compound (A) is 2,000 or more and 50,000 or less. The flexographic printing plate precursor according to any one of claims 1 to 5.
7. The emulsion compound (A) is a copolymerized polyester emulsion containing an aromatic polycarboxylic acid component as a copolymerization component and having a carboxyl group and / or a sulfonate group. The flexographic printing plate precursor according to any one of claims 1 to 6.
8. The intermediate layer contains the emulsion compound (B) in an amount of 10% by mass or more and 70% by mass or less based on the total amount of the intermediate layer. The flexographic printing plate precursor according to any one of claims 1 to 7.
9. The emulsion compound (B) is at least one emulsion compound selected from the group consisting of a polyurethane emulsion, a polybutadiene latex, a styrene-butadiene copolymer latex, and an acrylonitrile-butadiene copolymer latex. The flexographic printing plate precursor according to any one of claims 1 to 8.
10. a ratio of the emulsion compound (A) to the emulsion compound (B) is 1.0 or more and 2.3 or less; The flexographic printing plate precursor according to any one of claims 1 to 9.
11. The intermediate layer further contains an inorganic layered compound (C). The flexographic printing plate precursor according to any one of claims 1 to 10.
12. The intermediate layer further contains a crosslinking agent (D). The flexographic printing plate precursor according to any one of claims 1 to 11.
13. The thickness of the intermediate layer is greater than 2 μm and less than 30 μm. The flexographic printing plate precursor according to any one of claims 1 to 12.
14. An infrared irradiation step of laser ablating the infrared ablation layer of the flexographic printing original plate according to any one of claims 1 to 13 to produce a negative pattern; an exposure step of selectively exposing the photosensitive resin composition layer through the negative pattern; A development step of removing unexposed portions of the photosensitive resin composition layer. A method for manufacturing a flexographic printing plate.
15. The method includes: a printing plate manufacturing step of manufacturing a flexographic printing plate by the method for manufacturing a flexographic printing plate according to claim 14; and a printing step of printing using the flexographic printing plate manufactured by the printing plate manufacturing step. Flexographic printing method.
Citation Information
Patent Citations
Flexographic printing original plate
JP2013156495A
Photosensitive CTP flexographic printing original plate
JP2020046568A
Original plate for flexographic printing plate
JP2020140182A
Flexographic printing original plate and method for manufacturing flexographic printing plate
WO2020122001A1
Cited By
Flexographic printing plate master and method for manufacturing flexographic printing plates
JP7845592B1